Introgression shapes the genomic conflict landscape of Malus, providing evidence for a reticulate backbone in a woody crop lineage - Xiao-Ya Li; Zhao-Qian Niu; Ya-Wen Zheng; Jue-Lin Huang; Dai-Kun Ma; Jia-Xin Huang; Qiang Hao; Ti-Cao Zhang; Si-Yu Xie; Chao Xu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2026)

Fracture behavior and local damage characteristics of the rupture-affected region in Zr–Sn and Zr–Sn–Nb alloy cladding tubes after full-sequence LOCA testing - Yi Li; Bowen Qiu; Shengjia Zhao; Junfeng Wang; Wenjing Xie; Xu Ji; Shijie Wang; Kun Zhang; Tong Liu (Annals of Nuclear Energy, 2026)

Biocontrol potential of Bacillus velezensis lut-Y1: Antifungal lipopeptides against postharvest fungi Alternaria alternata and Penicillium expansum - Hui-Jun Yuan; Yan-Sen Li; Wen-Jin Ma; Tian-Kun Zhao; Zhen-Dong Wang; Miao-Miao He; Shi-Man Yu; Yan-Ying Xu (Physiological and Molecular Plant Pathology, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Microplastics on the toxicity of Ag+ and Cu2+ to Chlamydomonas reinhardtii: Exposure modes and modulation mechanisms - Banghao Du; Maolei Gong; Limei Xu; Zhen Yan; Jiayu Sun; Kun Liu; Fuxiang Guan; Qunqun Liu; Ruixue Jiang; Xiaochen Li (Environmental Pollution, 2026)

Topological planarization toward dielectric loss regulation - Jiaxiang Liu; Yulong Li; Kun Fan; Longbo Luo; Xu Wang; Xiangyang Liu (Chemical Engineering Journal, 2026)

Interconnection layer engineering and configuration matching for high-performance perovskite/PbS quantum dot tandem solar cells - Afei Zhang; Salman Ali; Gomaa Mohamed Gomaa Khalaf; Long Chen; Xinzhao Zhao; Jianbing Zhang; Kun Xu; Hsien-Yi Hsu; Li Wang; Mingyu Li; Haisheng Song (Chemical Engineering Journal, 2026)

Insights into the alleviating effects of exogenous α-ketoglutaric acid on free nitrous acid stress in Tribonema minus and ammonium removal in wastewater - Xinjuan Hu; Mingrui Wu; Teng Li; Xianhui Xue; Xu Yan; Baolong Wang; Lili Chen; Xiangru Xu; Lijuan Meng; Zhen Yu; Mostafa El-Sheekh; Guang Yang; et al. (Bioresource Technology, 2026)

Duplication and divergence: Two new Dmrt1 gene paralogs identified in autotetraploid Carassius auratus - Qian Xiao; Qingwen Xiao; Xu Huang; Yanlin Fu; Yuhan Yang; Chongqing Wang; Xiaowei Xu; Xidan Xu; Kun Zhang; Yue Zhou; Jinhai Bai; Zhengkun Liu; et al. (Aquaculture, 2026)

Arginine and putrescine ameliorate heat stress-induced testicular inflammation and apoptosis via inhibiting endoplasmic reticulum stress in mice - Kun Wu; Chenglong Yu; Guangmang Liu; Yong Zhuo; Bin Feng; Lianqiang Che; Shengyu Xu; Lun Hua; Jian Li; Zhengfeng Fang; De Wu; Yan Lin (Theriogenology, 2026)

Dynamic responses and seismic intensity measures of sea-crossing cable-stayed bridge under pulse-like ground motions considering fluid–structure interaction - Shenghao Xu; Qingtao Zheng; Junsheng Su; Yang Lv; Yu Chen; Kun Wu; Xiao Liang; Jie Li; Zhuolong Yan (Ocean Engineering, 2026)

Electrode fouling by extracellular proteins, rather than direct protection of algae, governs nanotip-enhanced electroporation failure in mesotrophic blooms - Peirui Liu; Kun Li; Yan Hong; Zhanfei He; Yiting Xu; Qianjin Xiang; Xiangliang Pan (Journal of Environmental Chemical Engineering, 2026)

A salt-tolerant dual-network hydrogel based on tea waste biochar for efficient seawater desalination - Kun-Xiu Liu; Yi-Bin Li; Lei Xu; Cai-Hua Liu; Zhu-Long Yu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2026)

Effects of localized heating body segments on the effectiveness of personal comfort systems in cold environments: A meta-analysis - Longde Chen; Kun Zhou; Shuting Li; Yankai Zhao; Hao Chen; Yi Xu (Energy and Buildings, 2026)

Ambient-air fabrication of high-performance thick-film organic solar cells enabled by solid additive engineering - Kun Li; Cunbin An; Yuan Yao; Jianbin Zhong; Bin Hu; Wei Zhang; Yishi Wu; Bowei Xu; Dianyi Liu; Guanghao Lu; Qing Liao; Xiaozhang Zhu; et al. (Chemical Engineering Journal, 2026)

High-pressure CO₂ spraying of electret melt-blown polypropylene for piezoelectric self-sensing respiratory monitoring masks - Jiahui Xu; Xiaoyue Zou; Ning Cao; Yunchen Yao; Yuxin Jia; Na Zheng; Zhenshu Chen; Youqiang Yang; Zhanquan Lu; Xiangrong Chen; Pengfei Xie; Cheng Li; et al. (Chemical Engineering Journal, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Cellulose nanofibril/polyvinyl alcohol hydrogel achieves efficient desalination of seawater and power generation based on Donnan effect - Kun Wang; Chong Li; Saifei Du; Zhangyu Zhu; Jiajie Xu; Wei Wang; Chunyan Hu; Dan Yu; Baojiang Liu (Carbohydrate Polymers, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Buffering rescue and microbial functional redundancy drive the synergy in ternary co-digestion of food waste, fallen leaves, and sewage sludge - Kun Li; Yan Li; Dongliang Hua; Yuxiao Zhao; Xufeng Yuan; Wenhao Liu; Meirong Xu; Irini Angelidaki; Haipeng Xu (Biomass and Bioenergy, 2026)

Synthesis of Template-polymerized β-cyclodextrin-based Cationic Microblock Flocculants for the Efficient Removal of Emulsified Oil - Kun Li; Wei Song; Erming Ouyang; Hongwei Yang; Yuxin Yuan; Songbiao Xu; Rui Zhao (Water, Air, & Soil Pollution, 2026)

Spatiotemporal variability of nitrate sources and transformations in the coastal waters of Wenzhou revealed by dual isotopes - Jiangnan Li; Qianhang Sun; Guohui Xu; Kun Lei (Journal of Contaminant Hydrology, 2026)

Precisely regulating the microenvironment towards robust active site for antibiotics degradation via Fenton-like reaction - Jiahao Cui; Wei Jian; Di Meng; Kun Wang; Jiaran Yao; Lina Li; Zijian Xu; Rile Ge; Junhu Wang; Jikun Li; Wonyong Choi; Yubao Zhao (Water Research, 2026)

Flood regime and dam operation jointly determine cyanobacterial dynamics in deep oligotrophic-mesotrophic reservoirs - Yu Qiu; Hai Xu; Wei Zou; Guangwei Zhu; Huiyun Li; Hans W. Paerl; Zhixu Wu; Kun Shi; Mengyuan Zhu; Boqiang Qin; Yunlin Zhang; Mingliang Liu (Water Research, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

First report of mass mortality in post-metamorphosis Magallana gigas associated with OsHV-1 in China: epidemiological and genomic characterization - Bo-Wen Huang; Xiang Zhang; Tao Xu; Yi-Tao Zhang; Xiao-Ai Li; Lei Gao; Ning Kong; Ming-Kun Liu; Tao Yu; Hui-Gang Kang; Chong-Ming Wang; Chang-Ming Bai (Journal of Invertebrate Pathology, 2026)

Investigating AHL-associated quorum sensing impact on antibiotic-driven resistome expansion in anaerobic fermentation microbiomes: Metagenomic insights - Qin Zhou; Xiangyue Xu; Kun Mi; Meixia Huo; Ziyan Kou; Ganwu Li; Lingli Huang (Journal of Environmental Management, 2026)

Associations of prenatal exposure to air pollution with fetal growth trajectories phenotype in a cohort study: Implications for child neurodevelopment - Xinmei Chen; Yinting Lin; Yi Lu; Deyi Zhuang; Aifen Zhou; Chenmiao Zhou; Kun Xu; Qinfen Li; Beibei Liu; Wei Xia; Shunqing Xu; Yuanyuan Li; et al. (Journal of Environmental Sciences, 2026)

Molecular characterization and differential immunomodulatory functions of TGF-β2 and TGF-β3 following Vibrio challenge in Takifugu obscurus - Fenfei Liang; Kun Liu; Xiaorui Zhou; Jinghan Wang; Yufeng Li; Yongqing Sun; Zhaoyang Li; Xin Liu; Yuwei Xu; Yihan Zhang; Guosong Zhang (Fish & Shellfish Immunology, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Corrigendum to “mussel-inspired multifunctional supramolecular hydrogel sensor enabled by machine learning for Morse code information communication” [Chem. Eng. J. 544 (2026) 178610] - Wanwan Li; Chang Xu; Wenqi Yang; Juanjuan Yang; Dengke Song; Jiawen Qiu; Wenlong Xu; Kangkang Zhou; Kun Dai (Chemical Engineering Journal, 2026)

Glucose- and pH-responsive nanozyme-integrated hydrogel with enzyme-like activity for MRSA infected diabetic wound healing - Pengchao Zhao; Dianhao Gong; Zhihui Ma; Huiying Yu; Xin Li; Zhixuan Li; Zimeng Xu; Yu Cao; Fangfang Fu; Chunshan Quan; Kun Lei (Chemical Engineering Journal, 2026)

Mussel-inspired multifunctional supramolecular hydrogel sensor enabled by machine learning for Morse code information communication - Wanwan Li; Chang Xu; Wenqi Yang; Juanjuan Yang; Dengke Song; Jiawen Qiu; Wenlong Xu; Kangkang Zhou; Kun Dai (Chemical Engineering Journal, 2026)

Organochloride compounds formation in chlorine-initiated styrene oxidation - Yinghong Sun; Kun Li; Li Xu; Narcisse Tsona Tchinda; Lin Du (Atmospheric Environment, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Influence of fines content and initial static shear on the cyclic liquefaction behavior of silty sands: A DEM study - Kun Pan; Peipei Li; Jiayu Wu; Wangcheng Xu; Zheng Hu; Yuxuan Wen; Yuanqiang Cai (Soil Dynamics and Earthquake Engineering, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Identification and expression profiling of SPL family genes in industrial hemp under NaHCO3 stress - Kun Cao; Xuehai Li; Jing Bian; Pan Wang; Hao Zhu; Pengfei Chu; Xiaoyan Zhang; Peiyu Chu; Hongwei Zhang; Tianliang Wang; Xu Han; Xiaonan Wang (Plant Gene, 2026)

Acute, chronic, and embryonic toxicity of bifenazate in Biomphalaria glabrata - Jialu Xu; Hairun Li; Jiyuan Wang; Hao Wu; Yuqing Shao; Ruke Wang; Lu Yang; Xinyi Fei; Anni Jin; Huiliang Zou; Kun Zhang; Xiaodong Yao; et al. (Journal of Hazardous Materials, 2026)

MIL-101(Cr) disrupts algal carbon fixation by intercepting photosynthetic electron flow: Implications for aquatic primary productivity - Kun Lu; Zian Wang; Yuxin Wang; Shuyang Chen; Na Li; Fangjie Guo; Lei Xu; Meizhen Wang (Journal of Hazardous Materials, 2026)

Synergistic gellan gum/flaxseed gum composite enhances freeze-thaw stability of soy isolate protein emulsion gels - Junxian Zhao; Yuan Xu; Atif Arshad; Mingru Zhang; Yue Sun; Xueling Li; Kun Gao; Jin Liang (Food Chemistry, 2026)

A health-oriented strategy for identifying and controlling high-risk PM2.5 sources: Case study of Heze - Xianmang Xu; Jingsen Zhao; Ying Li; Kun Liu; Chao Zhu; Lei Sun; Tao Li; Wenli Gu; Lidan Xu; Juan Dai; Jin Wang; Wei Cheng; et al. (Environmental Research, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Buffer-free BOZn coordination sites enable efficient Fe(VI) oxidation for organic pollutant removal - Xin-Jia Chen; Yu-Kun Huang; Ning Li; Pi-Jun Duan; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ying Shao; Xiao-Wei Xu; Jin-Song Guo; Fei Chen (Chemical Engineering Journal, 2026)

T2T reference genome and population genomic analysis provide insight into enhanced disease resistance in gynogenetic grass carp - Chongqing Wang; Yuchen Jiang; Jinhai Bai; Xu Huang; Xidan Xu; Xiaowei Xu; Kun Zhang; Yue Zhou; Zhengkun Liu; Siyang Li; Enkui Hu; Wanjing Peng; et al. (Aquaculture, 2026)

Characterizing brain structural and functional abnormalities in borderline personality disorder by seed-based d mapping approach - Wanru Qiu; Sen Li; Aoxue Zhang; Hao Yu; Jian Cui; Yinghong Xu; Liangliang Ping; Hao Zheng; Chunyu Dong; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2026)

Structural Response of Stiffened Panels Under Repeated Impacts from Rigid and Ice Hammers: An Experimental and Numerical Study - Nan Zhao; Yuwen Xu; Fei Li; Tongqiang Yu; Kun Liu (Journal of Marine Science and Engineering, 2026)
Repeated-impact tests were carried out on a typical stiffened panel using both a wedge-shaped ice indenter and, for comparison, a rigid steel indenter under identical conditions. The tests were performed on a drop-weight impact system under a mass-loaded configuration, and the impact force, deformation response, and failure characteristics were recorded. Numerical simulations were additionally conducted to analyze the structural response and damage evolution. Progressive permanent deformation was observed under both impact types, whereas ice impact produced stronger fluctuations and a more scattered peak-force history. The differences between the two impact modes are clarified, providing a reference for the impact-resistant design and safety assessment of ships designed for ice-covered water.

Intelligent identification and orientation information extraction of rock slope discontinuities from point cloud data based on LEKM-PointNet++ - Danni Zhao; Kun Li; Zixuan Zhang; Jiangbo Xu; Shengwen Qi; Peng Sha; Shaowei Wang; Guangming Luo; Bowen Zheng; Xiaolin Weng; Yalin Nan; Nengyuan Chen (Transportation Geotechnics, 2026)

Tumor-confined nano-activators for antigen-independent broad activation of tumor-infiltrating T cells - Yue Wang; Min Yang; Bao-Yue Zhang; Mei-Tang Peng; Yi-Qun Sun; Shi-Kun Zhou; Wei Li; Xian-Zhu Yang; Shi-Dang Xu; Zi-Dong Lu; Cong-Fei Xu; Jun Wang (Science Bulletin, 2026)

Engineered antibacterial-based repair peptide platform for the treatment of infected tissues - Hongchuan Wang; Liang Ma; Bide Tong; Shun Zhang; Gang Li; Huaizhen Liang; Hanpeng Xu; Di Wu; Zixuan Ou; Yifan Du; Shuchang Peng; Shihao Zhang; et al. (Chemical Engineering Journal, 2026)

Molecularly integrated dynamic chitosan network with topology-adaptive glucose/ROS responsiveness for coupled drug release and immunoregulation - Yuxiang Li; Sheng Dong; Ran Yu; Runjie Liu; Hengxi Xu; Hainuo Li; Wenbo Ming; Guochao Liao; Rong Zhang; Zhongqiu Liu; Wenxian Wang; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

Characteristics of the radar bright band observed over a high-altitude lake - Run Han; Yingying Chen; Xiaoyan Ling; Kun Yang; Xin Li; Junbo Wang; Changhui Zhan; Xu Zhou; Ming Chen (Atmospheric Research, 2026)

Insights from adaptive immune regulation for disease resistance breeding in livestock and poultry - Peiyao Yan; Kun Yang; Wenhao Xu; Jiarui Zhang; Wanting Zhong; Zhe Wang; Jiahui Zhang; Wenting Li; Kejun Wang; Yaofeng Zhao; Donghua Li; Shuyang Yu; et al. (Science China Life Sciences, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Correction: Machine learning-based correlation analysis of conventional water quality parameters and composite pollution index in the Luoqing river of the South China Sea Coastal Zone - JinYang Zhang; Yang Huang; JiaYu Yang; KaiYu Deng; HaiXiang Li; DunQiu Wang; YuFeng Xu; Kun Dong (Frontiers in Marine Science, 2026)

Dual repression of OsSnRK1β1A by the deubiquitinase OsOTUB1 orchestrates energy metabolism and grain yield in rice - Ludan Zhang; Pengfei Wang; Yue Li; Shuang Yang; Yan Chen; Zhiying Ma; Jing Pan; Xiaoyu Wang; Chenyan Wang; Haoyuan An; Yuqing Xu; Yifei Xiao; et al. (Molecular Plant, 2026)

Evaluation of Zanthoxylum bungeanum sprouts amino acids profile by capillary electrophoresis and principal component analysis - Chun-Mei Lv; Wen-Juan Shi; Xu-Kun Zhou; Wei-Feng Wang; Jun-Li Yang (Food Chemistry, 2026)

Aqueous biphasic systems based on dual deep eutectic solvents for simultaneous extraction and targeted partitioning of bioactive compounds from Cinnamomum cassia - Lili Zhang; Zhanghui Xie; Yuya Liu; Jianzhao Xu; Jipeng Liang; Mengfan Li; Lili Hu; Kun Hu; Jing Gao (Food Chemistry, 2026)

Retraction notice to “MOF-derived Cu@Cu2O nanoclusters for photothermally enhanced Fenton-like catalytic degradation of dye pollutants” [Environ. Res. 272 (2025)121178] - Ji Cheng; Zuojia Guo; Wenxuan Fan; Pan Xu; Hanjing Lu; Kun Cao; Ding Luo; Xiaoran Liu; Jinghua Li (Environmental Research, 2026)

Corrigendum to “Ionic crosslinking of alginate/carboxymethyl chitosan fluorescent hydrogel for bacterial detection and sterilization” [carbohydrate polymers, 302(2023) 120427] - Kun Yan; Yekai Wan; Feiyang Xu; Jing Lu; Chenguang Yang; Xiufang Li; Zhentan Lu; Dong Wang (Carbohydrate Polymers, 2026)

Accelerated proliferation of Kluyveromyces marxianus on glucose and xylose: Insights from adaptive laboratory evolution and MAPK/cell cycle genetic variations - Huiying Zhong; Kun Meng; Qing Peng; Xiaoqing Xu; Guozhen Li; Luqi Wang; Bo Shi; Yu Qiao (Bioresource Technology Reports, 2026)

Characterization, expression, and functional analysis of sarcospan (SSPN) in Chinese tongue sole: Cynoglossus semilaevis - Jing Yu; Yijing Yang; Tianwei Liu; Kun Huang; An Xu; Li Gong; Jing Liu; Fenghui Li; Denghui Zhu; Liqin Liu; Zhenming Lü (Journal of Oceanology and Limnology, 2026)

Isolation of new sesquiterpene glycosides from Dendrobium nobile and evaluation of their antitumor activity - Gu Min; Shu-chang Gao; Xiao-li Ma; Xiao-peng Huang; Yi-wei Chen; Xu-liu Shi; Jian-kun Yan; Xu-Hong Duan (Natural Product Research, 2026)

Improving growth performance across multiple sheep breeds by targeting the MSTN gene using an enhanced Cas12i system - Bo Liu; Huanyu Song; Miao Yan; Yu Wu; Pengfei Li; Zhanqing Fan; Yufei Chen; Yangsheng Wu; Jiapeng Lin; Liqin Wang; Xiaoyu Niu; Kun Xu; et al. (Science China Life Sciences, 2026)

Deep-learning reconstructed single-shot T2-weighted magnetic resonance imaging reveals subtle pancreatic duct injury in steroid-treated probable autoimmune pancreatitis - Meizi Li; Jia Xu; Kun He; Dong Wu; Aiming Yang (Science China Life Sciences, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

Exosomal lncRNA ENSSSCG00000049656 regulates porcine oocyte maturation via the ssc-miR-500-3p/EGLN2 axis - Junzheng Zhang; Yuyang Zhang; Hao Li; Jie Wang; Zhiwei Yao; Kun Zhao; Yang An; Shunfa Yao; Qinglong Xu; Shuang Ji; Yi Jin (Theriogenology, 2026)

Smoldering of crop residues emits a large amount of intermediate volatility organic compounds to the atmosphere - Hui Sun; Jinlong Wang; Wei Liu; Ling Ruan; Zhaomin Yang; Xueqi Ma; Xiaowen Chen; Li Xu; Lin Du; Qifan Liu; Kun Li (Journal of Hazardous Materials, 2026)

Recent advances in understanding the modulatory mechanisms of saliva in flavor perception - Kun Zhao; Zikang Xu; Yiyang Li; Qinguo Quan; Yuhan Xie; Juan Wang; Baoguo Sun; Dandan Pu (Food Chemistry, 2026)

Construction of HIPPEs based on sea bass protein-konjac glucomannan complexes for the delivery of astaxanthin, DHA and EPA - Lijuan Zhang; Ziyue Wang; Jiaxin Li; Zhe Xu; Kun Ma; Shuang Zhao; Tingting Li (Food Chemistry, 2026)

Manganese single-atom nanocubes as a bifunctional platform for tetracycline monitoring and remediation - Qingwen Dong; Xinkai Gu; Lixin Xu; Wuyang Huang; Hui Meng; Ming Li; Fang Zhu; Kun Zeng; Zhen Zhang (Chemical Engineering Journal, 2026)

An enhanced numerical model for predicting higher-harmonic wave loads based on weak-scatterer theory - Xinmeng Zeng; Yanlin Shao; Xingya Feng; Kun Xu; Wei Shi; Ruijia Jin; Huajun Li (Coastal Engineering, 2026)

Lignin-Regulated Carbon/Cobalt Co-Doped Graphite carbon nitride with synergistically enhanced Photo-PMS activation for efficient organic Pollutant degradation - Ying Xu; Wei Li; Kun Liu; Ting Xu; Guanhua Wang; Tairan Pang; Chuanling Si (Bioresource Technology, 2026)

Concomitant exposure to residential greenness, nitrogen dioxide, and outdoor light at night in association with incident anxiety - Jiayun Zhang; Yexiang Sun; Zihan Li; Lisha Xu; Jingjing Hu; Jie Qiu; Xinhan Zhang; Zongming Yang; Zhanghang Zhu; Yonghao Wu; Yixing Wang; Hongbo Lin; et al. (Landscape and Urban Planning, 2026)

Microcystin-LR-induced phosphorylation imbalance and organelle stress: An integrative review of autophagy dysregulation and cross-species toxicity - Zhuoran Teng; Asif Shahzad; Zhe Xu; Jiaojiao Xia; Jinshan Zhang; Yueli Ni; Wenjing Liu; Kun Cui; Yongping Li; Yurong Dong; Ziyuan Bai; Peng Zhang; et al. (Journal of Hazardous Materials, 2026)

Effects of cadmium-tolerant bacteria combined with biochar on cadmium and selenium dynamics in rice grown on seleniferous soils: Insights from a soil bacterial community analysis - Yanan Cheng; Jing Jiang; Lanping Song; Shangqi Xu; Meng Na; Kun Cheng; Daming Li; Shoubiao Zhou; Jihai Zhou (Journal of Environmental Chemical Engineering, 2026)

Metagenomic and transcriptomic insights into microbial activity maintenance strategies in a pilot-scale biosorption-biodegradation system for in situ sewer overflow treatment - Yunpeng Zhao; Yasong Chen; Zhengzhu Dang; Kun Li; Yating Zhu; Chaowei Xu; Xinyu Wan; Boyang Jia; Guangrong Cao; Qiushi Shen; Zheng Zhao (Journal of Environmental Management, 2026)

Elevation-driven divergence in soil colloid functionality governs polycyclic aromatic hydrocarbon mobility in the Three Gorges Reservoir riparian zone - Ying Xi; Jingzhong Long; Kun Li; Aoran Zhang; Biao Xiong; Tao Xu; David Johnson; Yuanfei Lv; Yingping Huang (Journal of Environmental Chemical Engineering, 2026)

Multi-head attention driven aggregation-differentiation network for probabilistic groundwater depth forecasting and depth-stratified early warning: A multi-site efficient framework - Jing Xu; Siyuan Liu; Jinran Wu; Yuming Mo; Kun Wang; Qingfeng Ji; You-Gan Wang; Ling Li (Environmental Modelling & Software, 2026)

Self-adhesive conductive hydrogel electronic skin for self-powered electrical stimulation to enhance antibacterial activity and accelerate wound healing - Yuxiu Liu; Kun Wang; Rongchen Xu; Yaqi Wang; Changzhen Xu; Yanghui Chen; Bingqi Zhao; Jianan Niu; Wei Sha; Jiangwen Wang; Xue Bai; Hongbo Li; et al. (Chemical Engineering Journal, 2026)

Fabricating nano- and micro- pesticide delivery systems using environmentally friendly humic acid - Kun Zhuang; Yue Xu; Zijun Wang; Xin Liu; Yunyu Tang; Xiangyang Li; Guang Wei; Hongyu Cao; Tingting Zhai; Feng Liu; Nan Zou; Peng Zhang; et al. (Chemical Engineering Journal, 2026)

Rhubarb-derived extracellular vesicles co-delivered with dexamethasone via multi-layered assembly nanostrategy for targeted ulcerative colitis therapy - Kun Wang; Mengqi Shen; Xu Luo; Lin Li; Ming Wu; Xiaotong Zhang; Huilin Zhu; Qian Du (Chemical Engineering Journal, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

Histomorphological analysis of the relationship between Helicobacter pylori infection of the gastric mucosa and host immunity strength - Yang-kun Wang; Quan-wei Guo; Hai-ying He; Ying-ying Li; Chao-ya Zhu; Ping Li; Bo Jiang; Su-nan Wang; Si-liang Xu (Journal of Molecular Histology, 2026)

Endoscopic prediction model for detecting advanced rectal polyps after ileorectal anastomosis in familial adenomatous polyposis: a dual-center retrospective study - Zhilin Liu; Xingjie Gao; Shuling Chen; Linfu Zheng; Binbin Xu; Gaozhen Deng; Wen Wang; Kun Lin; Chushu Li; Zhou Ye; Dazhou Li (Familial Cancer, 2026)

Development of global diffusion filling model for voids filling of Digital elevation models (DEMs) - Guoqing Zhou; Kun Li; Cong Li; Hanwen Gao; Ertao Gao; Xiang Zhou; Jiasheng Xu; Jianjun Chen (International Journal of Remote Sensing, 2026)

Efficient demulsification of emulsified oil wastewater by graft-functionalized β-cyclodextrin flocculants: The effect of charge density, hydrophobicity, and graft chain length - Erming Ouyang; Zhe Hu; Songbiao Xu; Wenjun Yang; Hongwei Yang; Kun Li; Rui Zhao (Water Research, 2026)

The key predictive factors of arbuscular mycorrhizal fungi community spatial distribution in saline-alkaline meadow soils: Abiotic variables or hosts? - Lin Zhang; Yuqiang Wen; Mengmeng Zhang; Kun Li; Ruotong Wu; Ning Sun; Fuqiang Song; Tianle Xu (Rhizosphere, 2026)

MdHMGB15 enhances zinc tolerance by activating multiple metal homeostasis genes in apple - Ran-Xin Liu; Ming-kun Wang; Yue-Ning Wang; Xiao-Han Qin; Ying-Xue Lv; Shan-Shan Li; Du Liu; Cong-Yu Xu; Xiao-Fei Wang (Journal of Hazardous Materials, 2026)

Amphiphilic Ti3C2/exfoliated bentonite@polyurethane sponge grafting both hydrophobic groups and polar oxygen-containing groups for efficient removal of multi-polar microplastics - Ting Huang; Shiqi Xu; Jing Li; Jiadong Wang; Yupei Yang; Luo Guo; Zisong Xu; Yue Xia; Kun Liu; Hanbing Zhang (Journal of Hazardous Materials, 2026)

Effects of anthropogenic activities on soil microbial communities and greenhouse gas fluxes in coastal wetlands of the Yellow River Delta, China - Jingyu Sun; Xiaoya Xu; Zihao Wang; Kun Li; Chenmiao Liu; Chen Li; Zhengxi Cai; Xinkun Zhao; Xinyi Xu; Hongjie Di; Qingfeng Chen (Journal of Environmental Sciences, 2026)

Magnetic properties driving nitrogen removal improvement in magnetite-enhanced activated sludge: Mechanistic insights and process validation - Jun Shi; Luo-Kai Li; Li-Han Lin; Duo-Kun Li; Jian Lu; Sali Mustafa Saleh; Tian-Yang Zhang; Huan He; Zheng-Yu Dong; Qian Xiao; Bin Xu; Chao Zeng (Environmental Research, 2026)

Bioinspired lignin-based coatings for durable and photothermal antibacterial surfaces - Cheng Wang; Bowen Ran; Kexin Li; Xiaodong He; Jing Li; Yunjie Xiang; Kun Xu; Xi Rao; Selvakumar Murugesan; Valentim A.R. Barão; En-Tang Kang; Liqun Xu (Chemical Engineering Journal, 2026)

Solar-driven catalytic platforms for closed-loop carbon cycling: CO2 assisting biomass conversion - Jingwen Jiang; Yiheng Wang; Yuanjie Li; Junxi Huang; Weiping Zhang; Dan Wang; Dong Xu; Dong Fu; Pan Zhang; Lemeng Wang; Kun Zhao (Bioresource Technology, 2026)

Assessing the Probiotic Properties and safety of Limosilactobacillus reuteri LP4 Isolated from Apis cerana Based on Whole Genome and Phenotype Analyses - Le Xu; Pingping Fang; Mingkui Lv; Shiyu Chen; Chen Liu; Sifan Wang; Jiqin Li; Kun Dong; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Research on Intelligent Identification of Dike Hidden Hazards Based on GprMax Forward Modeling and YOLOv11 Deep Learning: A Case Study of Wenzaobang River in Shanghai - Fu-yu Jiang; Run Han; Li-kun Gao; Jiong Ni; Jun-kai Yu; Xiao-yu Xu (Applied Geophysics, 2026)

Machine learning-based correlation analysis of conventional water quality parameters and composite pollution index in the Luoqing river of the South China Sea Coastal Zone - JinYang Zhang; Yang Huang; JiaYu Yang; KaiYu Deng; HaiXiang Li; DunQiu Wang; YuFeng Xu; Kun Dong (Frontiers in Marine Science, 2026)
Rivers serve as critical conduits for transporting pollutants and nutrients to coastal zones, directly influencing coastal ecosystem functions and marine environmental health. Understanding spatiotemporal variations and driving mechanisms of river water quality is therefore critical for effective watershed management and coastal zone protection. This study analyzed water quality data from three monitoring sections (Suqiao, Xialiang Village, and Longxi) along the Luoqing River in Guilin, China, collected during January 2023–March 2025. Seven conventional parameters—water temperature, pH, dissolved oxygen (DO), permanganate index (COD Mn ), total nitrogen (TN), total phosphorus (TP), and ammonia nitrogen (NH 3 -N)—were evaluated using Spearman correlation analysis, principal component analysis (PCA), and machine learning models (CatBoost, Random Forest, and XGBoost). The results showed pronounced monthly variability but relatively stable interannual patterns, indicating dominant control by seasonal hydrological and biogeochemical processes. Spatial differences were evident, with downstream sections exhibiting higher pollution levels and more complex parameter interactions, reflecting intensified anthropogenic influences. PCA extracted two principal components explaining over 70% of the total variance: PC1 associated with nutrient and organic pollution (TN, TP, NH 3 -N, COD Mn ) and PC2 representing physicochemical conditions (pH and DO). A Composite Pollution Index (CPI) was constructed based on NH 3 -N, TN, TP and COD Mn to characterize overall pollution levels. Machine learning models achieved high predictive performance for the CPI (R 2 ≈ 0.994). The shapley Additive Explanations (SHAP) and partial dependence analyses identified TN as the primary controlling factor, with synergistic enhancement between TN and COD Mn under high nitrogen conditions. Overall, Luoqing River water quality is characterized by a nitrogen-centered pollution structure, providing a scientific basis for targeted watershed management and coastal ecosystem protection.

An improved autotetraploid fish derived from the hybridization of gynogenetic homologous diploid crucian carp (♀) × autotetraploid carassius auratus (♂) - Yue Zhou; Ling Xiong; Xu Huang; Xi Dan Xu; Chongqing Wang; Xiaowei Xu; Kun Zhang; Jinhai Bai; Zhengkun Liu; Yuchen Jiang; Wanjing Peng; Enkui Hu; et al. (Aquaculture, 2026)

Active packaging based on nanocellulose-stabilized essential oil pickering emulsions: A review on enhanced properties and food preservation applications - Fan Li; Mengmeng Pang; Kun Liu; Shasha Lv; Quanfen Guo; Peide Cui; Wanqing Lei; Wei Liu; Xing Zhou; Ting Xu; Chuanling Si (Trends in Food Science & Technology, 2026)

Characteristics and techno-economic analysis of nickel-cobalt-manganese composite oxides produced by the flame synthesis method - Yunfei Xu; Wen Du; Junlei Wang; Haojie Guo; Shilong Li; Kun Wang (Journal of Cleaner Production, 2026)

Experimental study on the effect of pre-oxidation regulation on coal devolatilization and NOx emission during char combustion in O2/CO2/H2O atmosphere under pressurized conditions - Chenxi Bai; Wenda Zhang; Kun Chen; Sicong Xu; Yukai Li; Yijun Zhao; Shaozeng Sun; Dongdong Feng (Fuel, 2026)

Associations of concomitant exposure to outdoor light at night, air pollution, and greenness with metabolic syndrome: A cohort study in China - Lisha Xu; Yexiang Sun; Zihan Li; Jiayun Zhang; Yichao Dai; Ye Jiao; Zhanghang Zhu; Jingjing Hu; Jie Qiu; Yixing Wang; Hongbo Lin; Liming Shui; et al. (Environmental Research, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Source identification and health risks of heavy metals in Huixian Karst wetland sediments: a multi-model approach - Kun Dong; Jiayu Yang; Haixiang Li; Sze-Mun Lam; Jin-Chung Sin; Yufeng Xu; Dunqiu Wang (Environmental Geochemistry and Health, 2026)

A genetic algorithm-based approach for optimizing the interface configuration of segmental joints considering bending stiffness and bearing capacity - Li Zhang; Kun Feng; Ruoyang Tang; Chaojie Xiao; Boxue Xu; Jianming Zhou; Chuan He (Tunnelling and Underground Space Technology, 2026)

Complex terrain causes global model prediction biases of 21.7 Zhengzhou extreme precipitation - Peng Wei; Xin Xu; Ming Xue; Jian Li; Kun Zhao; Qinghong Zhang (Science Bulletin, 2026)

A critical review of sludge-based adsorbents: Application, recovery, regeneration, sustainable management, and feasibility assessment - Zhiliang Cui; Donghui Li; Kun Zhou; Xu Han; Jiayin Hao (Process Safety and Environmental Protection, 2026)

Prenatal exposure to indoor VOCs impairs synaptic plasticity and cognitive function in mouse offspring via retinol metabolism disorder - Jing Sun; Xin Zhou; Changjian Xiao; Zhuoyan Li; Caifang Xu; Xiji Qin; Jieru Lu; Yurong Wu; Jinping Cheng; Sun Chen; Jianyuan Zhao; Kun Sun (Journal of Hazardous Materials, 2026)

Failure patterns and hydrological response of layered slope - Junfeng Tang; Zhuxiang Ma; Maoshan Li; Junkai Xu; Taro Uchimura; Weimin Xiao; Xiangang Jiang; Dong Huang; Kun Fang (Geomorphology, 2026)

Synthesis of chitosan-phytic acid/TiO2 antioxidant composites for coal spontaneous combustion prevention - Yuanyuan Li; Xiaoling Xu; Ran Zhang; Xingbao Yang; Kun Jia (Fuel, 2026)

Improving the prediction performance of soluble solid content in bagged “Cuiguan” pear using Vis/NIR spectroscopy with spectral correction - Yiran Zhao; Qingqing Li; Changqing An; Kun Tao; Yida Yu; Huirong Xu (Food Control, 2026)

Structural and physicochemical changes of galactomannan during germination of Gleditsia sinensis seeds - Wei Xu; Yuchen Li; Yana Zhu; Minghui Han; Jian Zhou; Kun Wang; Li Ji; Jianxin Jiang (Carbohydrate Polymers, 2026)

Walkability, fine particulate matter and risk of Osteoporosis: A cohort study in China - Jie Qiu; Peng Shen; Jingjing Hu; Zhanghang Zhu; Lisha Xu; Jiayun Zhang; Zihan Li; Hongbo Lin; Liming Shui; Feng Tong; Kun Chen; Jianbing Wang (Atmospheric Environment, 2026)

Spatial variation of rainfall for landslide early warning: an examination from Majiajing watershed in Yunnan, China - Jing-Kun Bao; Kun Wang; Chuan-Bing Zhu; Ze Li; Ze-Min Xu; Yun-Fei Zhang; Lin Tian; Yang Yang; Jun-Yao Luo; Tai-Qiang Yang (Natural Hazards, 2026)

Mapping the Evolution of Experimental Autoimmune Encephalomyelitis Research (2000–2024): A Global Bibliometric and Knowledge Domain Analysis - Zhihua Dong; Yu He; Taisong Yin; Kun Xu; Xueli Liu; Hongxia Han; Lijuan Song; Zhibin Ding; Xinyi Li; Yanbing Su (Molecular Neurobiology, 2026)

Integrated multi-trophic aquaculture of sandfish Holothuria scabra with hard clam Meretrix taiwanica and milkfish Chanos chanos under environmental stress - Po-Kun Tseng; Min-Luen Tsai; Li-Xi Xu; Meei-Mei Chen; Yin-Hao Lai; Yu-San Han; Feng-Jie Su (Aquaculture International, 2026)

Shuyu capsule improves estrous cycle-dependent depression-like behavior in premenstrual dysphoric disorder (PMDD) mice by increasing GABAergic neuronal activation and downregulating GABAAR δ subunit expression in the dorsal periaqueductal gray (dPAG) region - Jialing Xu; Kun Liu; Yaru Cui; Hao Zhang; Xinyu Wang; Minghui Hu; Zifa Li; Peng Gao; Wei Liu; Mingqi Qiao; Wenqiang Cui; Xiwen Geng; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Advances in screening of saltiness-enhancing odorants: Transitioning from conventional sensory evaluation to intelligent high-throughput techniques - Qinguo Quan; Kun Zhao; Zikang Xu; Yiyang Li; Yuhan Xie; Fengyu Li; Baoguo Sun; Dandan Pu (Trends in Food Science & Technology, 2025)

A physically-refined regional climate model for the Tibetan Plateau - Kun Yang; Xu Zhou; Xiaogang Ma; Deliang Chen; Fahu Chen; Yongjiu Dai; Yaozhi Jiang; Anning Huang; Yanluan Lin; Jiarui Liu; Hui Lu; Jing Sun; et al. (Science Bulletin, 2025)

A plasma membrane receptor complex mediates early heat-responsive signaling to trigger nuclear transcriptomic reprogramming in Arabidopsis - Jing Li; Shifeng Wu; Kun Wang; Yang Xu; Xiaoyan Zhang; Xinru Li; Wen Song; Jian-Min Zhou; Zhizhong Gong; Shuhua Yang; Yanglin Ding (Molecular Plant, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

Mechanism of anomalous “internal subsidence and peripheral uplift” in a salt mine goaf: A multi-source validated superposition of poroelastic uplift and mining-induced subsidence - Ahu Zhao; Yinping Li; Xilin Shi; Shefeng Hao; Zengguang Che; Kun Yang; Mingnan Xu; Hongling Ma (Geomechanics for Energy and the Environment, 2025)

The impacts of global change on the self-thinning lines for six timber species in Canada - Yanni Pu; Cong Tang; Yujie Xiao; Sida Lai; Tong Jiang; Weifan Li; Pembegul Nozohourmehrabad; Kun Xu (Forest Ecology and Management, 2025)

Study on the effect of glycerol monostearate on the properties of sesame oil body-based aerated emulsions and related mechanisms - Delong Li; Yanpeng Zhang; Yue Long; Kun Zhang; Wei Xu; Chun Hu; Hailong Zhang (Food Chemistry, 2025)

Single-crystal layered oxide cathodes for sodium ion batteries: Mechanical failure and stabilized strategies - Kun Lin; Zhuomin Qiang; Shengwei Dong; Lin Zhou; Yanbin Ning; Yuqi Dong; Zhenxiang Xu; Dalong Li; Li Guan; Shuaifeng Lou (Chemical Engineering Journal, 2025)

Superefficient PM0.3 filtration and high-selectivity CO2 adsorption by MOF-activated poly(lactic acid) nanofibers - Li-Ning Dong; Cunmin Wang; Le Bao; Kun Yu; Yuzhen Hou; Xinjian He; Mengbao Fan; Shenghui Zhang; Shu-Gui Yang; Jiefeng Gao; Huan Xu (Chemical Engineering Journal, 2025)

Cellulose-engineered janus periosteum with compartmentalized angiogenic and osteo-immunomodulatory abilities for bone regeneration - Wuyan Xu; Kun Liu; Jiaqing Chen; Junliang Liu; Siming Li; Hua Wang; Binghong Luo; Qingqi Meng (Carbohydrate Polymers, 2025)

The MATE family transporter CaDTX12 confers cadmium accumulation in pepper (Capsicum annuum L.) - He Huang; Junwei Liang; Ali Raza; Xiaodong Li; Kun Lu; Weihong Xu (Functional & Integrative Genomics, 2025)

Associations between Plasma Metal Concentrations and Mortality Risk in Non-Small-Cell Lung Cancer Patients: A Prospective Cohort Study - Yan Liu; Xiao-Yun Chen; Jing-si Chen; Miao Xu; Hong-Jun Zhang; Quan Tang; Yu‑Song Zhang; Da‑Peng Li; Li-Qiang Qin; Kun Wang (Biological Trace Element Research, 2025)

Effects of seawater salinity variations on nitrogen transport in the coastal reservoir and adjacent aquifer - Yuming Mo; Jing Xu; Kun Wang; Beibei Xu; Jinran Wu; Qihao Jiang; Guangqiu Jin; Ling Li (Journal of Hydrology, 2025)

Detection of Escherichia coli O157:H7 in food based on magnetic separation and hybridization chain reaction - Ming Cai; Gaihua Wang; Xueting Cui; Tingyu Hou; Jun Wang; Kun Xu; Jinhua Li (Food Control, 2025)

Take-out containers as nano- and microplastics reservoirs: Diet-driven gut dysbiosis in university students - Chao Feng; Qian Zhang; Longmei Wang; Shuyuan Li; Kanglin Wang; Yifan Xu; Kun Chen; Jing Wang; Shujie Feng; Yi Lyu; Fengjie Tian; Cailing Wei; et al. (Environmental Pollution, 2025)

The influence of emotion on human thermal comfort: based on netted meta-analysis - Kun Zhou; Hao Yang; ShuTing Li; YaYu Feng; TianYi Pang; YanKai Zhao; Yi Xu (Energy and Buildings, 2025)

An intelligent flexible LIG/PDMS/AgNWs composite electronic skin with AI system for sports and health monitoring - Haoyuan Meng; Zongyuan Xu; Shipeng Zhang; Qingzhou Wang; Yufan Wang; Qihui Zhou; Ho-Kun Sung; Leonid Chernogor; Yuanyue Li; Zhao Yao; Yang Li (Chemical Engineering Journal, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

AI-driven smart mask-based respiratory monitoring system utilizing a high-performance and biocompatible PVA/PVP/graphene composite thermoelectric film - Zihe Li; Yongzhi Xu; Chenhao Li; Shengyu Xie; Qihui Zhou; Ho-Kun Sung; Leonid Chernogor; Zhao Yao; Yang Li; Yuanyue Li (Chemical Engineering Journal, 2025)

Effects of selenium–cadmium interactions on soil cadmium forms and the enrichment of selenium and cadmium in rice - Tianyi Lu; Yong He; Yanmei Ai; Meng Na; Shangqi Xu; Kun Cheng; Daming Li; Jihai Zhou (Plant and Soil, 2025)

CAR19-T/NK cell and circular aptamer–drug conjugate (ApDC) combination treatment increases immunotherapy efficacy - Ling-Qi Kong; Su-Yun Chen; Xu Cui; Ya-Hui Hu; Lian Wang; Jia-Yao Zhu; Lan-Xuan Guan; Bing-Kun Wang; Li-Ting Yang; Kai-Ming Chen; Chao-Ming Zhou (Molecular and Cellular Biochemistry, 2025)

Bacterial communities and C N cycling drive microplastic-specific trade-off between greenhouse gas emissions and antibiotic resistance genes during reductive soil disinfestation - Yanlong Chen; Fengyang Zhang; Yuhan Zhang; Risheng Xu; Jingyi Mei; Kun Wang; Cui Li; Fan Chen; Yuheng Wang (Applied Soil Ecology, 2025)

Positive effects of gamma aminobutyric acid on growth and lipopolysaccharide-induced intestinal mucosal barrier damage in snakehead (Channa argus) - Xue-qin Wu; Xu-nan Li; Feng-kun Cai; Yun-jie Lin; Xiao-tian Niu; Xiu-mei Chen; Yan-nan Tong; Gui-qin Wang (Aquaculture International, 2025)

Gynogenetic offspring from distant hybridization of red crucian carp × blunt snout bream: Insights into barbel origin - Zhengkun Liu; Xinyi Deng; Wanjing Peng; Siyang Li; Ling Xiong; Enkui Hu; Yan Tang; Zeyang Li; Qian Xiao; Yuhan Yang; Xu Huang; Chongqing Wang; et al. (Aquaculture, 2025)

Residential green space and transition trajectory of cardiometabolic multimorbidity in two prospective cohorts - Yonghao Wu; Jiacheng Ying; Yexiang Sun; Lisha Xu; Zihan Li; Jiayun Zhang; Jie Qiu; Yixing Wang; Jingjing Hu; Peng Shen; Hongbo Lin; Liming Shui; et al. (Urban Forestry & Urban Greening, 2025)

Exploring the impact of follicular fluid exosomes on porcine cumulus cell and oocyte function: Regulatory network analysis based on the ENSSSCG00000042788/ssc-miR-504/PDHA1 axis - Junzheng Zhang; Shuang Ji; Yue Han; Yuyang Zhang; Hao Li; Shunfa Yao; Qinglong Xu; Kun Zhao; Jie Wang; Zhiwei Yao; Yang An; Yi Jin (Theriogenology, 2025)

Integrative scATAC-seq and mtDNA mutation analysis reveals disease-driven regulatory aberrations in AML - Chen Tian; Yijun Dong; Xin Sun; Longchen Xu; Xiaoli Ma; Yuwei Tao; Fang Wang; Haohang Zhang; Jie Li; Kun Li; Yasong Chen; Hongxing Liu; et al. (Science Bulletin, 2025)

Elevated wet deposition of micro- and nanoplastics in remote mountains driven by free tropospheric transport - Buqing Xu; Yifan Li; Shizhen Zhao; Bolong Zhang; Jing Li; Jianchu Ma; Kun He; Linxiao Lu; Xiao Wang; Duohong Chen; Jun Li; Gan Zhang (Journal of Hazardous Materials, 2025)

Hydrofluoric-acid-mediated hydrothermal synthesis of anatase TiO2 with {101}/{001} facets for selective photocatalytic valorization of glycerol to syngas - Zheng Yang; Haoqiang Hou; Ermiao Liang; Kun Zhang; Mingcong Xu; Chunhui Ma; Wei Li; Sha Luo; Shouxin Liu (Journal of Environmental Chemical Engineering, 2025)

Enhancing black tea quality through shaking: Integrated metabolomic and transcriptomic analysis reveals the mechanism of shaking on quality-related components during tea processing - Mingjin Li; Hao Xu; Hongyu Chen; Qiuao Chen; Fengjiao Ding; Feiquan Wang; Naixing Ye; Xiaoli Jia; Kun Zhang; Shan Jin (Innovative Food Science & Emerging Technologies, 2025)

Pre-reduction of Goethite by hydroxylamine hydrochloride enhances sulfamethoxazole degradation via accelerated Fe(III)/Fe(II) cycling in Fenton-like systems - Hua Li; Kun Wang; Junge Xu; Tao Li; Yi Lu; Rusen Zou; Guanyu Zheng (Chemical Engineering Journal, 2025)

An ingenious structural design of NiCu-MOF bar-like nanosheet array: harnessing synergistic effects to attain exceptional ammonia oxidation performance - Guang-Lan Li; Yu-Hui Shi; Ri-Yang Huang; Tian-Ge Ma; Qian Zhuo; Ling Xu; Fei Jiang; Yu-Kun Zhai; Yong-Hou Xiao; Hong-Jiang Li; Yang Yan; Yun Zhao (Chemical Engineering Journal, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Nitrogen-salt interaction in Pennisetum giganteum: Effects on soil, rhizosphere, and ion transport processes - Peng Wang; Chen Zhang; Kok Sin Woon; Wenyu Li; Xu Pei; Mengxue Liu; Kun Zhang; Wenyan Li; Junkang Guo; Zhen Zhang; Yongtao Li (Applied Soil Ecology, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Precision-engineered lignin-based food packaging materials - Wei Li; Kun Liu; Hongbin Yang; Ying Xu; Meng Zhang; Tairan Pang; Liyu Zhu; Ting Xu; Guanhua Wang; Feng Shen; Chuanling Si (Trends in Food Science & Technology, 2025)

Amplified urban heat island effect in southern china’s old towns following atmospheric regulation policies - Junxiao Zou; Hans W. Chen; Haodong Li; Qiao Wang; Guoqiang Wang; Kun Jia; Ziyue Chen; Chuanfeng Zhao; Wenzhong Shi; Yinshan Yang; Yahui Tang; Jiayi Chen; et al. (Sustainable Cities and Society, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

ATP competition drives autophagy dysregulation by organic extracts of PM2.5 from solid fuel combustion on Tibetan Plateau - Jian Sun; Jiaer Yang; Yajing Ma; Zhang Yu; Lingli Li; Jinjin Yu; Xinyi Niu; Kun He; Hongmei Xu; Xiaofeng Niu; Xuhua Li; Zhenxing Shen (Journal of Hazardous Materials, 2025)

Epigenetic reprogramming of HDAC2 in CA1 excitatory neurons determines Pb-induced non-spatial memory deficits - Mengmeng Wang; Chengqing Huang; Shu Ai; Yanzhou Xia; Changqing Li; Yuxuan Zhi; Kun Wang; Ming Nie; Xiaozhen Gu; Yi Xu; Heyujia Zhang; Hui-Li Wang (Journal of Hazardous Materials, 2025)

Algal blooms in Lake Taihu: Earlier onset and extended duration - Jiangzhaoxia Chen; Xiaojie Gao; Xiaoke Xu; Chongjing Zhu; Xiaojun She; Debing Kong; Kun Xue; Yao Li (Harmful Algae, 2025)

Seismic performance of thin-flexible PEC column and H-section beam with end-plate connection joints - Wei Zhou; Kun Zhang; Bu-Shuan Li; Gen-Tian Zhao; Xue-Chun Liu; Xu-Ze Feng (Engineering Structures, 2025)

Bridging fault kinematics before, during, and after the 2022 Menyuan earthquake - Rumeng Guo; Wenting Zhang; Xiongwei Tang; Kun Dai; Yu Li; Dechuan Liu; Yong Zheng; Shiyu Zeng; Jiangcun Zhou; Jianqiao Xu; Heping Sun (Earth and Planetary Science Letters, 2025)

Quorum sensing-driven control of hydrogenotrophic biofilms: Toward energy-efficient wastewater treatment systems - Yuchao Chen; Wanying Yang; Lufeng Xu; Lijie Zhou; Minmin Jiang; Yufeng Xu; Dunqiu Wang; Xuehong Zhang; Kun Dong; Junjian Zheng; Haixiang Li (Chemical Engineering Journal, 2025)

A synergetic surface and bulk modification of 4.6 V LiCoO2 through nickel oxalate incorporated solid reaction synthesis - Lei Xu; Yajun Zhao; Sichen Jiao; Hongyi Pan; Jiacheng Zhu; Chengzhen Zhang; Penghao Chen; Kun Zhou; Bowei Cao; Yapei Li; Biao Deng; Juping Xu; et al. (Chemical Engineering Journal, 2025)

Bioinspired ECM-specific microenvironment scaffold: A multi-biomimetic strategy spatially guides osteochondral regeneration - Kun Liu; Wuyan Xu; Lin Li; Wendong Zhang; Wei Wen; Shan Ding; Mingxian Liu; Changren Zhou; Siming Li; Qingqi Meng; Binghong Luo (Chemical Engineering Journal, 2025)

Potential prognostic biomarker of OSBPL10 in pan-cancer associated with immune infiltration - Jiapeng Qi; Kun Yu; Bei Liu; Yan Wang; Wei Wang; Ran An; Chaojun Wang; Na Li; Dongqian Xu; Lin Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

BVDV antagonizes the antiviral activity of MDA5 by promoting its degradation via CCDC50-dependent selective autophagy - Zhen Wang; Shizhe Liu; Liang Xu; Jingyu Wang; Shaotang Ye; Siqi Cai; Kun Jia; Shoujun Li (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Assessing the performance of convection-permitting climate model in reproducing basin-scale hydrological extremes: A western Norway case study - Kun Xie; Lu Li; Hua Chen; Chong-Yu Xu (Journal of Hydrology, 2025)

Ultrasensitive and ultra-selective room-temperature H2S gas sensor based on CuO-loaded In2O3 2D porous nanosheets - Zhen Sun; Xueli Yang; Shaobin Yang; Kun Li; Xia Zhao; Lanxiang Yao; Wanru Xu; Haichao Wang; LanLan Guo; Guofeng Pan (Journal of Hazardous Materials, 2025)

Corrigendum to “Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations” [Comput. Geotech. 182 (2025) 107160] - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

Anodic dissolution behaviors of GH4049 superalloy in NaNO3 and NaCl solutions and its electrochemical machining for film cooling hole - Jingtao Wang; Jiabao Zhang; Xin Shi; Zhaoyang Zhang; Hao Zhu; Kun Xu; Yang Liu; Wei Xue; Tianlong Li; Jing Wang; Minglu Wang (Chemical Engineering Journal, 2025)

Will benefits of physical activity in reducing the risk of all-cause and cause-specific mortality be attenuated by exposure to air pollutant mixture? A prospective study in the UK Biobank - Hao Fu; Haijuan Xiong; Hao Bai; Yuanliang He; Zhaohui Zhang; Jianhao Xu; Jiayu Li; Fan He; Mengling Tang; Jianbing Wang; Kun Chen; Mingjuan Jin (Atmospheric Environment, 2025)

Breaking genetic linkage barriers to improve brown planthopper resistance and grain yield in japonica rice - Wenhui Wang; Jun He; Yunlong Wang; Na Li; Quanguang Sun; Menglong Zhang; Qi Li; Haosen Xu; Kun Shao; Shihao Zhang; Shijia Liu; Liangming Chen; et al. (Theoretical and Applied Genetics, 2025)

The combined effects of convective entrainment and orographic drag on precipitation over the Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Xiaoqi Xu; Xianghua Wu; Lei Zhu; Xin He; Shiying Wu; Pengcheng Lin (Science China Earth Sciences, 2025)

Numerical Modeling of Permeability Sensitivities Based on Characteristics of Heterogeneous Coal Structure Reservoirs - Rui Wang; Kun Zhang; Guofu Li; Liangwei Xu (Natural Resources Research, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Topological surface states in γ-PtBi2 evidenced by scanning tunneling microscopy - Yunkai Guo; Jingming Yan; Wen-Han Dong; Yongkai Li; Yucong Peng; Xuetao Di; Caizhen Li; Zhiwei Wang; Yong Xu; Peizhe Tang; Yugui Yao; Wenhui Duan; et al. (Science Bulletin, 2025)

Overexpression of the lectin receptor-like kinase gene OsLecRK-S.7 inhibits plant growth and enhances disease resistance in rice - Xiaoqun Peng; Yilin Li; Jingmei Xu; Ying Zeng; Kun Li; Xiangyi Guo; Zikang Zhang; Xiaoyan Tang; Menglong Wang (Plant Science, 2025)

AMF and biochar reshape the bacterial network in rhizosphere soil of Ricinus communis under chromium (Cr) stress and improve soil quality - Yuqiang Wen; Ruotong Wu; Tianle Xu; Ranran Cao; Ge Song; Dandan Qi; Wei Chang; Kun Li; Yuan Ping; Mengmeng Zhang; Xiaoxu Fan; Fuqiang Song (Journal of Hazardous Materials, 2025)

Associations of outdoor ozone concentration with thyroid function and the mediated role of serum metabolites: A panel study of healthy children - Huan Xu; Kun Huang; Biao Zhang; Huihua Yang; Jie Wang; Xinyue Li; Xia Meng; Renjie Chen; Xiaomin Zhang (Journal of Hazardous Materials, 2025)

NLRC3 regulates RIP2, STING, TBK1, and TRAF6 mediated type I IFN signaling and inflammatory response in large yellow croaker Larimichthys crocea - Yu Qing Xu; Ying Li; Kun Huang Han; Jia Xi Zhang; Kai Qing Li; Jing Jiang; Zhao Han Sun; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2025)

Corrigendum to “A novel ASGR1-Targeting nanocomplex for mitigating donor liver steatosis” [Chem. Eng. J. 513 (2025) 163089] - Xinwei Li; Yingying Liu; Deshu Dai; Huan Liu; Guangyao Zhang; Lianghao Zhang; Shangheng Shi; Peng Jiang; Bingliang Zhang; Zhiwen Zhao; Xuzhu Gao; Kun Yu; et al. (Chemical Engineering Journal, 2025)

Amphiphilic polyurethane-assisted uniform dispersion of TiO2/carbon dots hybrids in amidoximed polyarylene ether membranes for enhanced oil/water separation and photocatalytic organic dye degradation - Xingbao Yang; Junni Xie; Yuanyuan Li; Xiaoling Xu; Libo Hao; Qimeng Ran; Kun Jia (Chemical Engineering Journal, 2025)

Construction of PtFe/FeOx-Al2O3 interface via regulating the metal – support interactions for selective hydrogenation of cinnamaldehyde - Zequan Ma; Yilin Dong; Xu Tan; Jia Xue; Xiaoge Li; Yu Gu; Hui Shi; Lin-Wei Chen; Kun Wang; Lei Wang (Chemical Engineering Journal, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Review: application of machine learning methods to performance evaluation, lifetime prediction and integrated management of hydrogen fuel cells - Yingjie Xu; Xiaoke Li; Yang Cao; Kun Liu; Wuyi Ming (Environment, Development and Sustainability, 2025)

Efficient and anti-interference plastic classification method suitable for one-shot learning based on laser induced breakdown spectroscopy - Zhiying Xu; Xingyu Zhao; Xinying Peng; Kai Wang; Kedong Wang; Nan Zhao; Jiaming Li; Qingmao Zhang; Xueqing Yan; Kun Zhu (Chemosphere, 2025)

Formation of Sb2S3 photocatalyst during antimony removal from mine drainage by Shewanella sp. ANA-3 - Jinna Lu; Xiaohui Wu; Kaixiong Yang; Qiuyun Lou; Kun Xu; Li Ye (Journal of Water Process Engineering, 2025)

Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

A novel ASGR1-Targeting nanocomplex for mitigating donor liver steatosis - Xinwei Li; Yingying Liu; Deshu Dai; Huan Liu; Guangyao Zhang; Lianghao Zhang; Shangheng Shi; Peng Jiang; Bingliang Zhang; Zhiwen Zhao; Xuzhu Gao; Kun Yu; et al. (Chemical Engineering Journal, 2025)

Insights into changes in crust formation mechanisms across the Archean-Proterozoic Transition: Receiver function observations in the Capricorn Orogen, Western Australia - Tingzi Li; Liang Zhao; Jianfeng Yang; Xiaobing Xu; Kun Wang; Bo Wan; Ruth Murdie; Klaus Gessner; Simon Johnson; Huaiyu Yuan (Science China Earth Sciences, 2025)
The transition from the Archean to Proterozoic marks a critical period in Earth’s tectonic history, where primary crustal formation mechanisms may have shifted from vertical-accretion mantle plume tectonics to horizontal-accretion modern-style plate tectonics. Seismological evidence suggests that this regime shift might have left imprints in the crust of stable regions. However, due to sparse spatial and temporal sampling, there is no global consensus on whether seismic observations can infer the secular evolution of crustal characteristics. In this study, we utilized a dense seismic array deployed in the Capricorn Orogen of the West Australian Craton. By analyzing teleseismic receiver functions, we characterized the crustal V P / V S ratio and interface features across approximately two billion years of Archean to Proterozoic craton crust and correlated these observations with the two-stage Nd age model of surficial rocks. Our results indicate that during the Mesoarchean to Paleoproterozoic, crustal thickness in the Capricorn Orogen gradually increased. The changes of V P / V S ratio suggest a crustal evolution from felsic to more intermediate compositions, and the Moho gradient evolves from sharp to gradational. Significant crustal thickening and mafic compositions were observed along major block boundaries, accompanied by weak Moho amplitudes, and asymmetrically dipping Moho, spatially correlating with the Ophthalmia Orogeny (∼2.2 Ga) and the Glenburgh Orogeny (∼2.0 Ga). We propose that these changes in the crustal characteristic initially originated during these two collisional orogenies and were further modified by post-collision thermal and deformational events. Similar features are evident in seismic observations across many Precambrian subduction zones. Thus, we infer that around 2.2 to 2.0 billion years ago, primary crustal formation mechanisms in the West Australian Craton had transitioned to horizontal accretion modern plate tectonics. This study reveals the geometrical characteristics of Neoarchean to Paleoproterozoic subduction, providing new deep constraints for understanding the Archean-Proterozoic crustal accretion and geodynamic regime transitions.

Nrf2 Ameliorates Sevoflurane-Induced Cognitive Deficits in Aged Mice by Inhibiting Neuroinflammation in the Hippocampus - Junhua Li; Jinfeng Li; Yafang Liu; Chuwen Hu; Hui Xu; Dong Cao; Rong Zhang; Kun Zhang (Molecular Neurobiology, 2025)

Correction: Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Daily Evolution of Three-Dimensional Structure of a Subsurface Anticyclonic Eddy and Eddy-Induced Swirl Transport in the Canada Basin - Fan Xu; Haiyan Li; Ru Wang; Zhiqiang Wen; Kun Yang; Menghao Zhang (Journal of Ocean University of China, 2025)

Effects of anthropogenic activities on soil microbial community structure and methane anaerobic oxidation rate in coastal wetlands of Yellow River Delta, China - Chenmiao Liu; Zihao Wang; Xia Gao; Kun Li; Lei Yu; Jingyu Sun; Hongjie Di; Xiaoya Xu; Qingfeng Chen (Applied Soil Ecology, 2025)

Cadmium dominance in heavy metal pollution: ecological risks and human health implications in the Guan River Estuary, China - Wenjian Xu; Kun Meng; Wen Du; Zican Cai; Yanxia Li; Xiang Chen; Yimin Zhang (Frontiers in Marine Science, 2025)
Estuarine ecosystems are vulnerable to anthropogenic heavy metal pollution. This study examines cadmium (Cd) dominance in pollution and its ecological/human health impacts in China's Guanhe Estuary, a region heavily influenced by land-based inputs. Concentrations of six heavy metals (Cu, Pb, Zn, Cd, Cr, As) were measured in sediments and muscle tissues of 12 marine species across 11 sampling sites using atomic absorption and fluorescence spectrometry. Ecological risks were evaluated via pollution load index (PLI), geo-accumulation index (Igeo), and potential ecological risk index (E RI ). Health risks were assessed using target hazard quotient (THQ) and hazard index (HI). The results showed that the sediment concentrations of Cu, Pb, Zn, Cd, Cr, and As were 16.75±2.25, 8.39±0.91, 55.15±5.18, 0.10±0.01, 64.64±3.22, and 11.92±0.99 mg/kg, respectively. PLI and E RI indicated moderate pollution and low ecological risk, and Cd emerged as the primary pollutant and risk to ecology, based on its high Igeo and Er indices. Bioaccumulation analysis revealed that marine invertebrates, such as crabs, shrimps, and edible molluscs, accumulated higher concentrations of heavy metals, particularly Cd, compared to fish. Health risk assessments indicated no significant non-carcinogenic risks to local residents (THQ/HI < 1) for most metal species. Cd dominates due to human activities like agricultural/industrial runoff and high bioavailability in fine sediments. Despite low health risks, Cd hotspots near Liezikou Estuary and the double jetty need stricter controls and monitoring. These findings highlight Cd as a key contaminant, informing global estuary cleanup efforts.

Cortical thickness alternation in obsessive-compulsive disorder patients compared with healthy controls - Chunyu Dong; Hao Zheng; Hailong Shen; Yu Wan; Yinghong Xu; Ying Li; Liangliang Ping; Hao Yu; Chuanxin Liu; Jian Cui; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2025)

Integrated volatile metabolomics and transcriptomics provide insights into the formation of characteristic flavor in gynogenetic grass carp and its offspring - Jinhai Bai; Yan Tang; Xinyi Deng; Zhengkun Liu; Siyang Li; Enkui Hu; Ling Xiong; Wanjing Peng; Xu Huang; Chongqing Wang; Xidan Xu; Xiaowei Xu; et al. (Aquaculture, 2025)

Research on numerical simulation of initial process of sediment discharge from deep-sea mining vehicle - Kun Huang; Yong Zhao; Weijia Xu; Han Lu; Tianbao Bai; Li Zou (Ocean Engineering, 2025)

Transcriptomic profiling revealed the regulatory pathways and key genes associated with cold tolerance in two eel gobies - Jing Liu; Yantao Liu; Tianwei Liu; Cheng Zhao; Yuzhen Wang; Kun Huang; An Xu; Liqin Liu; Li Gong; Zhenming Lü (Journal of Thermal Biology, 2025)

In-situ formed SiC onto coal gasification residue (semi coke) to fabricate oxidation process-tolerable SiC/Ni2Si/SC composite for efficient microwave absorption in hot-air environment - Xiaojie Xue; Liping Liang; Xiuning Du; Kun Jia; Jiafa Xu; Kewei Zhang; Guomin Li (Fuel, 2025)

Oxidation mechanisms of ammonia and ethanol mixed fuel by using the ReaxFF-MD simulation - Chongchong She; Chunchen Xu; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

RETRACTED: MOF-derived Cu@Cu2O nanoclusters for photothermally enhanced Fenton-like catalytic degradation of dye pollutants - Ji Cheng; Zuojia Guo; Wenxuan Fan; Pan Xu; Hanjing Lu; Kun Cao; Ding Luo; Xiaoran Liu; Jinghua Li (Environmental Research, 2025)

Elucidating ozone formation mechanisms in the central Yangtze River Delta region, China: Urban and rural differences - Zhiqiang Liu; Wenlong Xu; Shengnan Zhu; Xin Zhang; Nan Xu; Siqi Wang; Kun Zhang; Ming Wang; Lam Yun Fat Nicky; Li Li (Environmental Pollution, 2025)

Thoracic perfusion of Esculentoside A-loaded thermosensitive hydrogel for the treatment of malignant pleural effusion in lung cancer - Jia You; Kun Shi; Xi Yang; Huawei Li; Lingnan Zheng; Yuanfeng Wei; JingYi Xu; Yue Li; Zhiyong Qian; Cheng Yi (Chemical Engineering Journal, 2025)

Biomass constructing double-layer 3D solar evaporator for highly-efficient seawater desalination and wastewater treatment - Donghuang Ouyang; Wenhua Xu; Kun Li; Songxi Hu; Mengmeng Wang; Jiarong Huang; Lingcao Tan; Shuping Xiao; Baiping Xu; Heng Xie (Chemical Engineering Journal, 2025)

Dynamic covalent synthesis of highly-crystalline and fully-cyclized aromatic COF as an artificial interphase layer toward stable lithium metal batteries - Wei Shao; Da Xu; Tiantian Wang; Huanghao Pan; Ying Liu; Xue Gao; Jiahuan Luo; Jing Wang; Zhong-Kun Li; Yao Guo; Huihui Zhao; Ning Fu; et al. (Chemical Engineering Journal, 2025)

Structural characterizations and antiaging activities of hydrolyzed low-molecular-weight polysaccharides from Polygoni Multiflori Radix Praeparata - Wei Xu; Xue-Jian Li; Yu-Sen Zhong; Jia-Qi He; Wei Xie; You-Kun Kang; Hua-Zhong Ying; Chen-Huan Yu (Carbohydrate Polymers, 2025)

Arbuscular mycorrhizal fungi-mediated formation of different carbon fractions in various wetland types enhances carbon sequestration post-restoration on the Tibetan Plateau - Lei Du; Size Liu; Shengqiang Wang; Jia Yang; Biao Tang; Kun Li; Jingchao Zhou; Ya Xu; Yufeng Ye; Yongqi yang; Hao Tang (CATENA, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Serum Proteomics Analysis of Patients with Ascending Aortic Dilation - Kun Liu; Yuchen Wang; Zhidong Ye; Zixuan Chen; Yanyan Liang; Feng Shen; Xiangdong Meng; Jian Liu; Lichun Guan; Wenyi Yang; Jingjing Hu; Shiping Xu; et al. (Cardiovascular Toxicology, 2025)

Association of temporal self-regulation theory and its constructs with eating behavior: A systematic review and meta-analysis - Shuang Wu; Xiaonan Hao; Danhua Qu; Xuetong Zhao; Xinyi Zhao; Jingwen Xu; Yan Xiao; Kun Li (Appetite, 2025)

Comprehensive studies on optimization and control effectiveness of tuned viscous mass dampers (TVMDs) in long-span bridges with floating systems - Kun Xu; Minghui Li; Ruisheng Ma; Qiang Han; Xiuli Du (Engineering Structures, 2025)

Enhancing the flutter performance of long-span bridges through using inerter-based dynamic vibration absorbers - Kun Xu; Zhenchuan Li; Shiming Ren; Genshen Fang; Kaiming Bi; Qiang Han (Engineering Structures, 2025)

Sludge reduction using polyvinyl alcohol-sodium alginate (PVA/SA)-immobilized refined iron ore and microorganisms: Optimization and mechanism - Shicheng Xie; Hao Wei; Liang Xu; Kun Pu; Xuan Li; Junfeng Su (Chemical Engineering Journal, 2025)

Development of a high-resolution near-surface meteorological forcing dataset for the Third Pole region - Yaozhi Jiang; Wenjun Tang; Kun Yang; Jie He; Changkun Shao; Xu Zhou; Hui Lu; Yingying Chen; Xin Li; Jiancheng Shi (Science China Earth Sciences, 2025)

The synergistic effect of Rhizophagus irregularis and Biochar on the growth of Switchgrass under sodium-saline-alkali stress: insights from soil mechanical property analysis - Yuqiang Wen; Tianle Xu; Wei Chang; Kun Li; Xiaoxu Fan; Yuan Ping; Fuqiang Song (Mycorrhiza, 2025)

The Influence of Heterogeneous Processes on the Physicochemical Properties of Atmospheric Aerosols - Maofa Ge; Shengrui Tong; Lin Du; Lingyan Wu; Ting Lei; Kun Li; Minglan Xu; Narcisse T. Tsona; Wenqian Zhang; Hailiang Zhang (Advances in Atmospheric Sciences, 2025)
With the rapid development of the world economy, complex air pollution has increasingly become a serious threat; for example, with haze events occurring frequently in various regions of the globe. Recent evidence has indicated that secondary aerosols play an important role in haze formation, and that heterogeneous processes are among the main forces driving their explosive growth. In this regard, this paper reviews recent advances in the understanding of the impact of heterogeneous processes on haze chemistry, including the impact on NO 2 chemistry, marine aerosols, and the hygroscopicity and optical properties of atmospheric aerosols. It is distinguished from past reviews on this topic by focusing mainly on new insights from the past five years. We summarize the main findings of the impacts of heterogeneous processes on NO 2 chemistry, marine aerosols, and the physicochemical properties of atmospheric aerosols, and propose several future research directions.

Advancing predictive, preventive, and personalized medicine in eyelid diseases: a concerns-based and expandable screening system through structural dissection - Jing Cao; Kun You; Peifang Xu; Yiming Sun; Ji Shao; Yifan Zhou; Huimin Li; Lixia Lou; Qi Miao; Juan Ye (EPMA Journal, 2025)
Background/aims Early recognition of eyelid morphological abnormalities was crucial, as untreated conditions could lead to blinding complications. An eyelid screening system that could provide both anatomical and pathological information was essential for formulating personalized treatment strategies. This study aimed to develop a clinically concerns-based framework capable of identifying common eyelid diseases requiring further intervention by evaluating individual anatomical and pathological changes. This approach would enhance individualized and efficient prevention, while supporting targeted treatment strategies. Methods The eyelid disorder screening system, Eyetome, was developed based on a morphological atlas and comprised four modules designed to identify 14 common eyelid disorders and pathological changes. A total of 6180 eye patches were analyzed to extract anatomical and pathological features. The performance of Eyetome was evaluated using average accuracy (aACC) and F1 score, with comparisons made against traditional models and ophthalmologists. To assess the system’s expandability, an additional test was conducted in a multimorbidity scenario. Results Eyetome demonstrated high performance in recognizing single diseases, achieving an aACC of 98.83% and an F1 score of 0.93. The system outperformed classic models, with an aACC of 98.83% compared to 96.72% for Desnet101 and 97.59% for Vit. Additionally, Eyetome’s aACC exceeded that of a junior ophthalmologist (JO) (97.11%) and was comparable to a senior ophthalmologist (SO) (98.69%). In the extended multimorbidity dataset, Eyetome maintained robust performance with an accuracy of 97.97%, surpassing JO (95.47%) and closely matching SO (97.81%). Conclusions This study developed a clinical concerns-based system for screening and monitoring eyelid disorders, aimed at supporting predictive diagnosis, preventing diseases progression, and facilitating more effective, patient-centered treatment of common eyelid disorders, aligning with the principles of predictive, preventive, and personalized medicine (PPPM/3PM). The system’s interpretability, scalability, and user-friendly data acquisition design could further enhance its acceptance among both doctors and patients, facilitating the shift from reactive medicine to proactive precision medicine.

Recent advances on Bi12O17Cl2-based photocatalysts for energy and environmental application - Xiao-Ju Wen; Xiao-Hang Qiao; Yu-Xin Li; Hai Guo; Hao-Zhe Li; Xian-Kun Wu; Bin-Bin Qian; Qi-Hui Xu; Zong-Tang Liu; Zheng-Hao Fei (Journal of Cleaner Production, 2025)

New insights into quercetin's attenuation of TBBPA-induced injury to MCEC cells: Involvement of the p38/NF-κB pathway and pyroptosis - Ke Li; Kun Wang; Tong Xu; Chencong Lyu; Xuejiao Yang; Hongjin Lin; Shiwen Xu (Journal of Environmental Management, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

The role of miRNAs in the associations between particulate matter and ischemic stroke: A nested case-control study - Tiezheng Li; Lisha Xu; Peng Shen; Jie Qiu; Yixing Wang; Jingjing Hu; Peng Guan; Hongbo Lin; Zhiqin Jiang; Kun Chen; Jianbing Wang (Environmental Pollution, 2025)

Hierarchical coaxial heterostructure enabled by thermal annealing cobalt nanowires for stable lithium anodes - Yang Xu; Gang Li; Kun Li; Jiangtao Hai; Haotian Weng; Hewei Yuan; Yanjie Su; Nantao Hu; Yafei Zhang (Chemical Engineering Journal, 2025)

Strigolactone and karrikin receptors regulate phytohormone biosynthetic and catabolic processes - Liangliang Li; Aarti Gupta; Chenbo Zhu; Kun Xu; Yasuko Watanabe; Maho Tanaka; Motoaki Seki; Keiichi Mochida; Yuri Kanno; Mitsunori Seo; Kien Huu Nguyen; Cuong Duy Tran; et al. (Plant Cell Reports, 2025)

CircXPO6 promotes breast cancer progression through competitively inhibiting the ubiquitination degradation of c-Myc - Aiqi Xu; Xi Li; Qiaoting Cai; Ciqiu Yang; Mei Yang; Hongfei Gao; Minyi Cheng; Xianzhe Chen; Fei Ji; Hailin Tang; Kun Wang (Molecular and Cellular Biochemistry, 2025)

Evaluation of Antibiotic-Sensitive Bacillus Strain as a Potential Probiotic for Enhanced Growth in Penaeus vannamei - Yiwen Gu; Ke Xu; Zhuoran Chen; Yanxu Lu; Shuguang Fang; Kun Hu; Xin Ju; Liangzhi Li; Zhi Chen (Current Microbiology, 2025)

A review of research progress on COF-based biosensors in pathogen detection - Xiang Li; Xi Zheng; Yanhui Yuan; Jiahui Deng; Liang Su; Kun Xu (Analytica Chimica Acta, 2025)

Diet shift and allometric growth in the early development Odontobutis potamophila - Miao Xiang; Kun Xiao; Hongliang Xu; Bo Li; Hongxi Guo; Zhanhu Yang; Chuankun Zhu; Man Wang; Jie Wang; Wei Xin; Songguang Xie; Xiaoming Zhu; et al. (Aquaculture, 2025)

The impact of temperature regulation measures on the thermodynamic characteristics of bee colonies based on finite element simulation - Yuntao Lu; Wei Hong; Wei Wu; Jie Zhang; Shijuan Li; Baohua Xu; Kun Wei; Shengping Liu (Biosystems Engineering, 2025)

“Tire plastisphere” in aquatic ecosystems: Biofilms colonizing on tire particles exhibiting a distinct community structure and assembly compared to conventional plastisphere - Zixuan Zhang; Jia Zhao; Kun Li; Xun Wang; Hongzhe Xu; Deqiang Mao; Sheng Liu (Journal of Hazardous Materials, 2025)

Ultrasensitive aflatoxin B1 detection based on vertical organic electrochemical transistor - Shuai Zhang; Kai Xiao; Kejie Zhang; Peng Li; Li Wang; Caizhang Wu; Kun Xu (Food Chemistry, 2025)

Efficiently radiation-induced degradation and extraction of Polygonatum sibiricum polysaccharides and its excellent ROS scavenging properties - Dong-Xu Tang; Shi-Zhong Zhou; Zhi-Jun Wang; Yang-Lin Zhang; Kun Liu; Jin-Yu Yang; Xiao-Jie Yang; Yue-Sheng Li; Xia Zhang (Chemical Engineering Journal, 2025)

Mechanism of cadmium (Cd) enrichment in the soil of karst areas with high geochemical background in Southwest China - Bo Li; Kun Lin; Xu Liu; Xudong Ma; Xuezhen Li; Zhiliang Wu; Cheng Li; Tao Yu; Tiansheng Wu; Zhongfang Yang (Chemical Geology, 2025)

Exaptation of pectoral fins for olfaction in the spiny red gurnard (Chelidonichthys spinosus) through an ancient receptor - Lisen Li; Deqian Fan; Chenglong Zhu; Zhuoya Liu; Wenji Huang; Peidong Xin; Huishan Yue; Mengying Li; Yufei Wang; Wenjie Xu; Jiangmin Zheng; Ye Li; et al. (Science China Life Sciences, 2025)

Design and synthesis of N-aryl-2-trifluoromethyl-quinazoline-4-amine derivatives as potential Werner-dependent antiproliferative agents - Huimin Li; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Jiaomei Wei; Chang You; Kun Liu; Menghan Wang; Xueling Meng; Guangcan Xu; Heng Luo; et al. (Molecular Diversity, 2025)

PRELP inhibits colorectal cancer progression by suppressing epithelial-mesenchymal transition and angiogenesis via the inactivation of the FGF1/PI3K/AKT pathway - Xiaoqing Li; Zhongxiang Jiang; Junfeng Li; Kun Yang; Jin He; Qianxi Deng; Shuman Xu; Zhihang Jiang; Fuqiang Liu; Zheng Jiang (Apoptosis, 2025)

Construction of lignin-containing cellulose nanofibers based superhydrophobic membrane for effective oil-water separation - Jian Huang; Kun Zhou; Beiqiu Chen; Siyu Li; Qiong Wang; Xuepeng Lin; Yunhe Xie; Pingfan Xu; Xin Lin; Chunxiang Lin (Journal of Water Process Engineering, 2025)

Hydrogeochemical processes of As enrichment and migration in the Surface’s critical zone of the Shiquan River basin in the western Qinghai–Tibet Plateau - Qingshan Li; Xiaobing Kang; Mo Xu; Ke Li; Kun Zhu (Journal of Hydrology, 2025)

3D fluorinated honeycomb cavity morphology through modulated crystal facet for dendrite-free aqueous zinc batteries - Zhihong Luo; Mengxuan Zhou; Jianwei Lu; Tingting Xu; Xiangqun Zhuge; Xiyuan Zhong; Laijun Liu; Yibing Li; Kun Luo; Xinyu Li; Weiwei lei; Dan Liu (Chemical Engineering Journal, 2025)

Unsteady hydrate film controlled mechanism of rapid hydrate formation: From pilot to pore scales - Xuan Kou; Heng Zhang; Xiao-Sen Li; Kun Wan; Rui Xu; Yi Wang (Chemical Engineering Journal, 2025)

Engineering atomic Pt-N3 sites on CdS nanorods for overcoming the rate-determining organic dehydrogenation in photocatalytic coproduction of H2 and value-added chemicals - Huanmin Liu; Jiayi Peng; Xu Zhang; Kun Zheng; Lirong Zheng; Kangle Lv; Qin Li; Peng Zhou (Chemical Engineering Journal, 2025)

Constructing chromium-tolerance La0.6Sr0.4Co0.2Fe0.8O3-δ cathode for solid oxide fuel cells using entropy-assisted surface engineering - Xu Han; Qi Shao; Kaixin Li; Yuan Gao; Bo Wei; Zimin Cai; Kun Zheng; Peizhong Feng; Zhe Lv; Yihan Ling (Chemical Engineering Journal, 2025)

Biomimetic superparamagnetic gelatin/chitosan asymmetric fibrous membrane for accelerating wound healing under static magnetic field - Jingxi Wang; Kun Li; Yunxue Jia; Tianran Song; Junwei Xu; Xuemei Sun; Meili Liu; Ping Li; Yubo Fan (Carbohydrate Polymers, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Enhanced mite control and agricultural safety with etoxazole-loaded chitin nanocrystals: Synthesis, characterization, and ecological impacts - Xu Zhifeng; Feng Guo; Zhang Chenghao; Xia Wei; Li Maoyan; Qian Kun; Zhang Yongqiang (Pesticide Biochemistry and Physiology, 2024)

Study on the development of the vortex street between the wings of wave glider - Yongguo Li; Kun Zhang; Xuan Tang; Caiyin Xu; Xiangyan Li (Ocean Engineering, 2024)

Restoration from grazing on the Tibetan plateau: Pathway-specific soil MAOC sequestration in meadow and peat wetlands - Lei Du; Size Liu; Yang Ding; Xiaomei Pan; Kun Li; Jia Yang; Ya Xu; Jingchao Zhou; Yufeng Ye; Yongqi yang; Hao Tang (Journal of Environmental Management, 2024)

Outdoor light at night, air pollution and risk of incident type 2 diabetes - Yonghao Wu; Ye Jiao; Peng Shen; Jie Qiu; Yixing Wang; Lisha Xu; Jingjing Hu; Jiayun Zhang; Zihan Li; Hongbo Lin; Zhiqin Jiang; Liming Shui; et al. (Environmental Research, 2024)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

Effects of antimony on antioxidant system, damage indexes of blood-brain barrier and ultrastructure of zebrafish (Danio rerio) - Kun Xu; Haitao Zou; Aijiang Yang; Qin Yao; Qing Li; Jingyun Zhang; Xia Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Low-coordinated Fe−N3 single atom with rapid protonation for boosting oxygen reduction reactions - Shiyu Li; Meihuan Liu; Xu Zhang; Xiaoxia Chen; Chudi Ni; Yiwen Chen; Hanwen Hu; Kun Zheng; Hui Su (Chemical Engineering Journal, 2024)

Coagulopathy-independent injectable catechol-functionalized chitosan shape-memory material to treat non-compressible hemorrhage - Dong Xiang; Kunlan Wang; Feilong Wang; Yan Li; Yulin Hou; Kun Hu; Yongxiang Xu (Carbohydrate Polymers, 2024)

Embryonic Genome Activation (EGA) Occurred at 1-Cell Stage of Embryonic Development in the Mud Crab, Scylla paramamosain, Revealed by RNA-Seq - Li-Kun Xu; Chun-Yan Ma; Feng-Ying Zhang; Wei Wang; Ming Zhao; Xin Jin; Jin-Ju Yin; Ling-Bo Ma; Wei Chen; Jia-Yuan Xu; Ke-Yi Ma; Zhi-Qiang Liu (Marine Biotechnology, 2024)

Cooling effects of urban parks under various ecological factors - Zhiqiao Li; Qin Liu; Kun Yan; Donghong Xiong; Pei Xu; Yangyang Yan; Liyang Lin (Urban Climate, 2024)

Seasonal and long-term variations of nutrients in Liaodong Bay, China: Influencing factors and ecological effects - Jinhao Wu; Zhaohui Wang; Jiashen Tian; Nan Li; Kun Wang; Lun Song; Guangjun Song; Xuemei Xu (Marine Environmental Research, 2024)

Preparation, physicochemical and functional characterization of pectic polysaccharides from fresh passion fruit peel by magnetic-induced electric field-assisted three-phase partitioning - Saiyin Yu; Jing-Kun Yan; Ming-Yu Jin; Long-Qing Li; Ya-Hui Yu; Li Xu (Food Hydrocolloids, 2024)

PoCXCL8, a teleost chemokine, exerts direct bactericidal, chemotactic/phagocytic, and NETs releasing properties, promoting host anti-bacterial immunity - Kun-yu Zhao; Guan-yu Chen; Hui Huang; Xu-dong Jiao; Xue-peng Li; Jian Zhang (Fish & Shellfish Immunology, 2024)

Engineering the interfacial hetero-structure for high-current-density hydrogen evolution - Bai Xu; Jiabin Xu; Junhui Hu; Shuo Li; Yong Feng; Cheng Lu; Kunming Hou; Lina Li; Kun Feng; Jun Zhong (Chemical Engineering Journal, 2024)

Unveiling potential sex-determining genes and sex-specific markers in autotetraploid Carassius auratus - Kun Zhang; Xu Huang; Chongqing Wang; Xidan Xu; Xiaowei Xu; Xiaoping Dong; Qingwen Xiao; Jinhai Bai; Yue Zhou; Zhengkun Liu; Xinyi Deng; Yan Tang; et al. (Science China Life Sciences, 2024)

Long-term changes of surface ozone and ozone sensitivity over the North China Plain based on 2015–2021 satellite retrievals - Chuanyong Zhu; Yichao Gai; Zhenguo Liu; Lei Sun; Siyuan Fu; Kun Liu; Leifeng Yang; Guang Pan; Baolin Wang; Chen Wang; Na Yang; Zhisheng Li; et al. (Air Quality, Atmosphere & Health, 2024)

Emerging therapeutic avenues against Cryptosporidium: A comprehensive review - Munwar Ali; Chang Xu; Jia Wang; Muhammad Fakhar-e-Alam Kulyar; Kun Li (Veterinary Parasitology, 2024)

Calibration of wave-induced high-frequency dynamic response and its effects on the fatigue damage of floating offshore wind turbine - Haozhe Bai; Min Zhang; Wei Li; Kun Xu; Huajun Li (Ocean Engineering, 2024)

PoIL8-L, a teleost interleukin-8 like, enhances leukocyte cellular vitality and host defense against bacterial infections in Japanese flounder (Paralichthys olivaceus) - Kun-yu Zhao; Yue Fang; Rong-jing Xu; Jian Zhang; Bin Sun; Xue-peng Li (Fish & Shellfish Immunology, 2024)

Bayesian finite element model updating with a variational autoencoder and polynomial chaos expansion - Qiang Li; Pinghe Ni; Xiuli Du; Qiang Han; Kun Xu; Yulei Bai (Engineering Structures, 2024)

Comparison of NaNi1/3Fe1/3Mn1/3O2 and Na4Fe3(PO4)2(P2O7) cathode sodium-ion battery behavior under overcharging induced thermal runaway - Qinghua Gui; Bin Xu; Kun Yu; Xinyu Wang; Jinzhong Li; Yuguang Xie; Ran Yu; Xiaochong Zhou; Lei Mao (Chemical Engineering Journal, 2024)

A novel analytical solution for horizontal vibration of partially embedded offshore piles considering the distribution effect of wave loads - Benlong Wang; Chunyi Cui; Chengshun Xu; Kun Meng; Jingbo Li; Lina Xu (Ocean Engineering, 2024)

Comprehensive assessment of the water environment carrying capacity based on machine learning - Hua Zhang; Huaming Li; Xiangqin Xu; Xubo Lv; Jiayu Peng; Qiaoran Weng; Wenhui Wang; Kun Lei (Journal of Cleaner Production, 2024)

Resources, energy consumption and economic analysis for flame synthesis of ternary cathode materials - Wen DU; Junlei WANG; Yunfei XU; Shilong LI; Kun WANG (Journal of Cleaner Production, 2024)

Surface fluorination of nickel nanowires enabling LiF-rich nanoscale solid electrolyte interface for stable lithium anodes - Yang Xu; Lu Yao; Hewei Yuan; Haotian Weng; Kun Li; Bin Li; Xiaolu Huang; Yanjie Su; Nantao Hu; Yafei Zhang (Chemical Engineering Journal, 2024)

Efficacy of melanin-loaded lipoic acid-modified chitosan hydrogel in diabetic wound healing - Zixuan Pang; Qianyun Li; Kun Liu; Xiaopei Wu; Haixing Xu; Zhenbing Chen; Honglian Dai (Carbohydrate Polymers, 2024)

A crustal radially anisotropic shear-wave velocity model of Northwestern Australia - Tingzi Li; Liang Zhao; Rijin Zhao; Ruth E. Murdie; Klaus Gessner; Xiaobing Xu; Kun Wang; Bo Wan; Sergi Ventosa; Huaiyu Yuan (Precambrian Research, 2024)

CCL2 Potentiates Inflammation Pain and Related Anxiety-Like Behavior Through NMDA Signaling in Anterior Cingulate Cortex - Huan Guo; Wen-chao Hu; Hang Xian; Yun-xin Shi; Yuan-ying Liu; Sui-bin Ma; Kun-qing Pan; Sheng-xi Wu; Li-yan Xu; Ceng Luo; Rou-gang Xie (Molecular Neurobiology, 2024)

IGFBP2 induces podocyte apoptosis promoted by mitochondrial damage via integrin α5/FAK in diabetic kidney disease - Xiaochen Wang; Yifan Zhang; Kun Chi; Yuwei Ji; Keying Zhang; Ping Li; Zhangning Fu; Xu Wang; Shaoyuan Cui; Wanjun Shen; Guangyan Cai; Xiangmei Chen; et al. (Apoptosis, 2024)

Microbiome analysis reveals alteration in water microbial communities due to livestock activities - Chang Xu; Sijia Lu; Yangji Cidan; Hongzhuang Wang; Guangming Sun; Muhammad Usman Saleem; Farid Shokry Ataya; Yanbin Zhu; Wangdui-Basang; Kun Li (Environmental Science and Pollution Research, 2024)

Spatiotemporal Variations in Trophic Diversity of Fish Communities in a Marine Bay Ecosystem Based on Stable Isotope Analysis - Pengcheng Li; Wan Chen; Kun Wang; Binduo Xu; Chongliang Zhang; Yupeng Ji; Yiping Ren; Ying Xue (Fishes, 2024)
Climate change has led to significant fluctuations in marine ecosystems. As a component of the food web, the trophic diversity and spatiotemporal changes of fish communities are crucial for understanding ecosystems. In recent years, stable isotope analysis has been increasingly used as a comprehensive tool for quantitative assessment of trophic diversity to explore spatiotemporal variations in fish community diversity. This study is based on carbon (δ13C) and nitrogen (δ15N) stable isotope analysis using different biomass-weighted isotope diversity indices, including isotopic divergence index (IDiv), isotopic dispersion index (IDis), isotopic evenness index (IEve), and isotopic uniqueness index (IUni). The overall results indicate that IDis, IEve, and IUni values of fish communities were relatively low, while IDiv was relatively high in the Haizhou Bay ecosystem. IDiv, IDis, IEve, and IUni were lower in autumn than in spring; IDiv and IDis were relatively higher in offshore waters, while IEve and IUni were relatively higher in inshore waters. The changes in species composition and intensive pelagic–benthic coupling in Haizhou Bay may lead to significant spatiotemporal variations in the trophic diversity of fish communities in the area. These findings highlight the importance of incorporating trophic relationships into ecosystem models, which will help to enhance our understanding of the complexity of the trophic structure of fish communities.

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Subway station flood risk management level analysis - Yongwei Gong; Xinxin Xu; Kun Tian; Zhuolun Li; Mengge Wang; Junqi Li (Journal of Hydrology, 2024)

Intelligent regional subsurface prediction based on limited borehole data and interpretability stacking technique of ensemble learning - Jun Bai; Sheng Wang; Qiang Xu; Junsheng Zhu; Zhaoqi Li; Kun Lai; Xingyi Liu; Zongjie Chen (Bulletin of Engineering Geology and the Environment, 2024)

Two-stage optimization for the air conditioning system in public buildings with flexible control of indoor load - Shibo Li; Xingying Chen; Le Bu; Kun Yu; Jun Shen; WenLi Xu; Jinfan Chen (Energy and Buildings, 2024)

A novel strategy for enhancing the stability of aptamer conformations in heavy metal ion detection - Shi Quan Qian; Min Yuan; Xian Wei Zuo; Hui Cao; Jin Song Yu; Li-Ling Hao; Kun Lin Yang; Fei Xu (Analytica Chimica Acta, 2024)

A Neural-network-based Alternative Scheme to Include Nonhydrostatic Processes in an Atmospheric Dynamical Core - Yang Xia; Bin Wang; Lijuan Li; Li Liu; Jianghao Li; Li Dong; Shiming Xu; Yiyuan Li; Wenwen Xia; Wenyu Huang; Juanjuan Liu; Yong Wang; et al. (Advances in Atmospheric Sciences, 2024)

Characteristics and mechanisms of soil structure damage under salt weathering - Zhao Duan; Kun Song; Ning Zhang; Li-Cai Zheng; Xu-Sheng Yan; Meng-Meng Zhang (Soil and Tillage Research, 2024)

Quantum spin driven Yu-Shiba-Rusinov multiplets and fermion-parity-preserving phase transition in K3C60 - Shu-Ze Wang; Xue-Qing Yu; Li-Xuan Wei; Li Wang; Qiang-Jun Cheng; Kun Peng; Fang-Jun Cheng; Yu Liu; Fang-Sen Li; Xu-Cun Ma; Qi-Kun Xue; Can-Li Song (Science Bulletin, 2024)

Pressure monitoring and deformation analysis of a brine-filled salt cavern - A case study of Jianghan, China - Peng Li; Yinping Li; Xilin Shi; Xinxing Wei; Kun Yang; Hongling Ma; Chunhe Yang; Wei Hu; Hao Xu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

Rhombohedral platinum-copper intermetallic compound: A high phosphate tolerance electrocatalyst for HT-PEMFC - Wenrui Zhang; Sheng Xu; Yunxu Yang; Qingwei Gao; Sheng Zhu; Kun Ding; Qiaoxia Li; Penghui Shi; Yulin Min (Chemical Engineering Journal, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Analyte-perturbed balance between reducibility and fluorescence of Ti3C2 MXene quantum dots for label-free, dual-mode detection of silver ions - Peng Jin; Pingping Wan; Chunyan Zhang; Xu Li; Yan Wang; Jianxin Luo; Kun Li (Analytica Chimica Acta, 2024)

A new polysaccharide from leaves of Sabia parviflora - Sijing Wu; Hui Li; Manshu Li; Bang Xu; Chengxiong Liu; Kun Zou (Natural Product Research, 2024)

The influence of in situ purification system on pathogen in the river fed by the drainage of sewage plant - Zhao-xu Peng; Yu He; Lu-ji Yu; Zi-yao Hao; Ting-mei Li; Li-kun Gu; Li Wang (Environmental Science and Pollution Research, 2024)

D-beta-hydroxybutyrate up-regulates Claudin-1 and alleviates the intestinal hyperpermeability in lipopolysaccharide-treated mice - Ting Wang; Yuchen Zhuang; Chenglong Yu; Zhaobo Wang; Yuan Liu; Qian Xu; Kun Liu; Yanning Li (Tissue and Cell, 2024)

Supporting function of vegetation in urban riparian ecological corridors for ground-dwelling faunal diversity in Beijing, China - Mengyuan Zhang; Shuxin Fan; Xiaolu Li; Yitong Li; Kun Li; Yiding Xu; Li Dong (Science of The Total Environment, 2024)

Proteomics revealed composition- and size-related regulators for hepatic impairments induced by silica nanoparticles - Xinying Zhao; Ru Ma; Alimire Abulikemu; Yi Qi; Xiaoying Liu; Ji Wang; Kun Xu; Caixia Guo; Yanbo Li (Science of The Total Environment, 2024)

In-situ electron capture by surface Co-Ci to facilitate the solar water splitting of Fe2O3 - Chang Li; Cheng Lu; Ye Zhu; Shuo Li; Yong Feng; Yiliu Yang; Bai Xu; Kun Feng; Jun Zhong (Chemical Engineering Journal, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Genomic data and ecological niche modeling reveal an unusually slow rate of molecular evolution in the Cretaceous Eupteleaceae - Kun-Li Xiang; Sheng-Dan Wu; Lian Lian; Wen-Chuang He; Dan Peng; Huan-Wen Peng; Xiao-Ni Zhang; Hong-Lei Li; Jia-Yu Xue; Hong-Yan Shan; Gui-Xia Xu; Yang Liu; et al. (Science China Life Sciences, 2024)

Devonian integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Wenkun Qie; Kun Liang; Wen Guo; Biao Gao; Junjun Song; Bo Chen; Pu Huang; Li Qiao; Honghe Xu; Jitao Chen; Yucong Sun; Yichun Zhang (Science China Earth Sciences, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Imbalance of T follicular helper cell subsets trigger the differentiation of pathogenic B cells in idiopathic membranous nephropathy - Bishun Deng; Huijie Huang; Li Deng; Ziling Zhao; Miao Liu; Haibiao Lin; Xiaowan Wang; Ruimin Tian; Xiaoxin Tu; Anping Peng; Enyu Liang; Kun Bao; et al. (Inflammation Research, 2024)

Hydroxyapatite and its composite in heavy metal decontamination: Adsorption mechanisms, challenges, and future perspective - Ting Wang; Weiyuan Cao; Kun Dong; Haixiang Li; Dunqiu Wang; Yufeng Xu (Chemosphere, 2024)

FvDFR2 rather than FvDFR1 play key roles for anthocyanin synthesis in strawberry petioles - Xinyu Li; Xi Luo; Zhongchi Liu; Chong Wang; Anqi Lin; Kun Xiao; Minghao Cao; Junmiao Fan; Hongli Lian; Pengbo Xu (Plant Science, 2024)

Genetically engineering of Saccharomyces cerevisiae for enhanced oral delivery vaccine vehicle - Baoquan Han; Feng Yue; Xiaojun Zhang; Kun Xu; Zhiying Zhang; Zhongyi Sun; Lu Mu; Xiaoyu Li (Fish & Shellfish Immunology, 2024)

Study on structure and properties of galactomannan and enzyme changes during fenugreek seeds germination - Yana Zhu; Wei Xu; Chi Feng; Liwei Zhu; Li Ji; Kun Wang; Jianxin Jiang (Carbohydrate Polymers, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Single-cell transcriptome analysis of liver immune microenvironment changes induced by microplastics in mice with non-alcoholic fatty liver - Wangrui Liu; Meng Li; Huaqi Guo; Shiyin Wei; Wenhao Xu; Yuanliang Yan; Yaoping Shi; Zhijie Xu; Kun Chang; Gang Wei; Shuai Zhao (Science of The Total Environment, 2024)

CsIL-20, a tongue sole interleukin-20, negatively mediates leucocyte activity and antibacterial defense - Kun-yu Zhao; Hui Huang; Qiu Jin; Lei Wang; Xu-dong Jiao; Xue-peng Li (Fish & Shellfish Immunology, 2024)

Exosomes derived from adipose tissues accelerate fibroblasts and keratinocytes proliferation and cutaneous wound healing via miR-92a/Hippo-YAP axis - Zifei Shao; Jinghao Xu; Xiang Wang; Yuxi Zhou; Yujing Wang; Yiyang Li; Jianping Zhao; Kun Li (Journal of Physiology and Biochemistry, 2024)

Development and experimental validation of a machine learning-based disulfidptosis-related ferroptosis score for hepatocellular carcinoma - Cong Zhang; Tiantian Xu; Kun Ji; Shoujin Cao; Jing Ai; Junhan Pan; Yunbo Cao; Yuning Yang; Li Jing; Jun-Hui Sun (Apoptosis, 2024)

Environmental selenium and human longevity: An ecogeochemical perspective - Bo Li; Xu Liu; Tao Yu; Kun Lin; Xudong Ma; Cheng Li; Zhongfang Yang; Qifeng Tang; Guodong Zheng; Jianxun Qin; Ying Wang (Chemosphere, 2024)

Experimental determination and QSAR analysis of the rate constants for SO5•− reactions with aromatic micropollutants in water - Yihui Zhang; Kun Lu; Wenyu Wang; Juntao Guo; Yongrong Zou; Jing Xu; Jinjun Li; Ivan P. Pozdnyakov; Feng Wu (Chemosphere, 2024)

Study on the lateral thermal disturbances of three parallel embankments on permafrost along the Gonghe-Yushu Engineering Corridor in China - Binhua Hu; Long Jin; Yanhui Niu; Zhipeng Fu; Xu Li; Yuanhong Dong; Kun Yuan; Ziqiao Zhao (Transportation Geotechnics, 2024)

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

The central Qiangtang Metamorphic Belt in northern Tibet is an in-situ Paleo-Tethys Ocean: Evidence from newly discovered Late Devonian radiolarians - Xin Li; Noritoshi Suzuki; Yi-chun Zhang; Hua Zhang; Mao Luo; Dong-xun Yuan; Quan-feng Zheng; Wen-kun Qie; Qi Ju; Feng Qiao; Hai-peng Xu; Xiao-hui Cui (Gondwana Research, 2024)

Co-based metal-organic frameworks confined N-hydroxyphthalimide for enhancing aerobic desulfurization of diesel fuels - Dongao Zhu; Kun Zhu; Lixian Xu; Haiyan Huang; Jing He; Wenshuai Zhu; Huaming Li; Wei Jiang (Fuel, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Exosomes Derived from Human Adipose Mesenchymal Stem Cells Inhibits Fibrosis and Treats Oral Submucous Fibrosis via the miR-181a-5p/Smad2 Axis - Zifei Shao; Jinhao Xu; Xiaoyang Xu; Xiang Wang; Yuxi Zhou; Yiyang Li; Kun Li (Tissue Engineering and Regenerative Medicine, 2024)
BACKGROUND: Oral submucous fibrosis (OSF) is a chronic disease with carcinogenic tendency that poses a non-negligible threat to human health. Exosomes derived from human adipose mesenchymal stem cells (ADSC-Exo) reduces visceral and cutaneous fibroses, but their role in OSF has received little attention. The aim of this study was to investigate the effects of ADSC-Exo on OSF and elucidate the mechanism. METHODS: In brief, ADSCs were extracted from adipose tissues and subjected to flow cytometry and induction culture. Fibroblasts were isolated from human buccal mucosa and subjected to immunofluorescence. Myofibroblasts were obtained from fibroblasts induced by arecoline and identified. Immunofluorescence assay confirmed that myofibroblasts could take up ADSC-Exo. The effects of ADSC-Exo on the proliferative and migratory capacities of myofibroblasts were examined using the Cell Counting Kit-8 and scratch assay. Real-time quantitative polymerase chain reaction (qPCR) was performed to evaluate mothers against decapentaplegic homolog 2 (Smad2), Smad3, Smad7, collagen type 1 (Col1), Col3, alpha smooth muscle actin (α-SMA), fibronectin, and vimentin. Western blotting was performed to detect phospho (p)-Smad2, Smad2, p-Smad2/3, Smad2/3, Smad7, Col1, Col3, α-SMA, fibronectin, and vimentin. Furthermore, the dual-luciferase reporter assay was performed to prove that miR-181a-5p in ADSC-Exo directly inhibited the expression of Smad2 mRNA to regulate the transforming growth factor beta (TGF-β) pathway. We also performed qPCR and western blotting to verify the results. RESULTS: ADSC-Exo could promote the proliferation and migration of myofibroblasts, reduce the expressions of p-smad2, Smad2, p-smad2/3, Smad2/3, Col1, αSMA, fibronectin, and vimentin and elevated the levels of Smad7 and Col3. In addition, miR-181a-5p was highly expressed in ADSC-Exo and bound to the 3'-untranslated region of Smad2. ADSC-Exo enriched with miR-181a-5p reduced collagen production in myofibroblasts and modulated the TGF-β pathway. CONCLUSIONS: ADSC-Exo promoted the proliferative and migratory capacities of myofibroblasts and inhibited collagen deposition and trans-differentiation of myofibroblasts in vitro . miR-181a-5p in exosomes targets Smad2 to regulate the TGF-β pathway in myofibroblasts. ADSC-Exo perform antifibrotic actions through the miR-181a-5p/Smad2 axis and may be a promising clinical treatment for OSF.

Spatially varying relationships of soil Se concentration and rice Se concentration in Guangxi, China: A geographically weighted regression approach - Bo Li; Xu Liu; Chaosheng Zhang; Tao Yu; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Lei Wang; Kun Lin; Xudong Ma; Xuezhen Li; Husheng Zhang; et al. (Chemosphere, 2023)

Influence of the perceived neighborhood environment on Paying for domestic waste management services in rural China: Evidence from the Xiangtan Prefecture - Yang Zhang; Kun Zhang; Congyan Liu; Fangshu Li; Bing Xu (Utilities Policy, 2023)

Efficient degradation and detoxification of antibiotic Fosfomycin by UV irradiation in the presence of persulfate - Jingyi Wu; Zhe Xu; Kun Yao; Zhu Wang; Ruobai Li; Linzi Zuo; Guoguang Liu; Yiping Feng (Science of The Total Environment, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

Integrated wearable foam modified with WS2 nanosheets@MoS2 quantum dots for oral disease diagnosis and healthcare monitoring - Fangyu Shi; Juanrui Du; Qi Han; Fanrou Zhang; Kun Wang; Zitong Kan; Lin Wang; Chunyan Li; Lin Xu (Chemical Engineering Journal, 2023)

Production of all-male non-transgenic zebrafish by conditional primordial germ cell ablation - Fang Wang; Yong-Yong Feng; Xu-Guang Wang; Mi Ou; Xin-Cheng Zhang; Jian Zhao; Kun-Ci Chen; Kai-Bin Li (Fish Physiology and Biochemistry, 2023)

Landslide susceptibility assessment in Qinzhou based on rough set and semi-supervised support vector machine - Chunfang Kong; Yu Li; Kun Dong; Yiping Tian; Kai Xu (Earth Science Informatics, 2023)

Soil microbial communities as potential regulators of N2O sources in highly acidic soils - Junhui Yin; Huaihai Chen; Pengpeng Duan; Kun Zhu; Naihui Li; Yan Ma; Yumeng Xu; Jingheng Guo; Rui Liu; Qing Chen (Soil Ecology Letters, 2023)

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

Synthesis and evaluation of in vitro and in vivo anti -Toxoplasma gondii activity of tetraoxane-substituted ursolic acid derivatives - Ya-Lan Wang; Li-Li Jin; Xu Cheng; Wei-Feng Yan; Hao Deng; Qing-Kun Shen; Zhe-Shan Quan; Chun-Mei Jin; Chang-Hao Zhang (Natural Product Research, 2023)

Toxic effects of environmentally persistent free radicals (EPFRs) on the surface of tire wear particles on freshwater biofilms: The alleviating role after sewage-incubation-aging - Kun Li; Deyue Kong; Xiaojia Xiu; Wanqi Hao; Defu Xu (Chemosphere, 2023)

Prediction of cadmium contents in rice grains from Quaternary sediment-distributed farmland using field investigations and machine learning - Xudong Ma; Tao Yu; Dong-Xing Guan; Cheng Li; Bo Li; Xu Liu; Kun Lin; Xuezhen Li; Lei Wang; Zhongfang Yang (Science of The Total Environment, 2023)

Comparison of improved hybrid FTS models for forecasting the urban air quality index - Kun Dong; Peng Ran; Qinyang Fan; Xu Liu; Weiqi Li (Journal of Cleaner Production, 2023)

The improvement of the oxidative oat (Avena sativa L.) protein based on ultrasound treatment: Study of structural, emulsifying, and rheological properties - Yue Xu; Yang Yang; Chun-min Ma; Xin Bian; Li-Kun Ren; Bao-xiang Liu; Lian-zhong Ai; Na Zhang (Food Hydrocolloids, 2023)

Carbonate rocks as natural buffers: Exploring their environmental impact on heavy metals in sulfide deposits - Kun Lin; Tao Yu; Wenbing Ji; Bo Li; Zhiliang Wu; Xu Liu; Cheng Li; Zhongfang Yang (Environmental Pollution, 2023)

Enhanced sensitivity and detection range of a flexible pressure sensor utilizing a nano-cracked PVP hierarchical nanofiber membrane formed by BiI3 sublimation - Dedong Guo; Shuheng Dong; Qingzhou Wang; Huixin Yu; Eun-Seong Kim; Qing Xu; Ho-Kun Sung; Zhao Yao; Yuanyue Li; Nam-Young Kim (Chemical Engineering Journal, 2023)

Tandem c-cl cleavage and oxidation over Pt/ZSM-5 catalysts for CH2Cl2 deep oxidation: Acidity – Redox synergy, rate – Limiting step, and catalyst stability - Yu-Kun Ma; Li-Li Xu; Long-Ren Ouyang; Lu-Lu Huang; Ai-Ping Jia; Yu Wang; Ji-Qing Lu (Chemical Engineering Journal, 2023)

Mesoporous SiO2 anode armour for lithium oxygen battery - Hailiang Mu; Kun Luo; Yaming Pang; Xiangqun Zhuge; Zhengping Ding; Yurong Ren; Degui Li; Zhihong Luo; Ben Bin Xu; Maryam Bayati; Xiaoteng Liu (Chemical Engineering Journal, 2023)

Role of nitrogen dual reaction sites in N-doped graphene aerogels for synergistic sulfamethoxazole adsorption and peroxymonosulfate activation in Fenton-like process - Ning An; Shijing Li; Bentuo Xu; Linbo Qian; Yi Shen; Kun Wang; Xiangyu Li; Min Zhao; Xiangyong Zheng; Renlan Liu (Chemical Engineering Journal, 2023)

Distinct and shared endothermic strategies in the heat producing tissues of tuna and other teleosts - Baosheng Wu; Xueli Gao; Mingling Hu; Jing Hu; Tianming Lan; Tingfeng Xue; Wenjie Xu; Chenglong Zhu; Yuan Yuan; Jiangmin Zheng; Tao Qin; Peidong Xin; et al. (Science China Life Sciences, 2023)

Feeding-induced plant metabolite responses to a phoretic gall mite, its carrier psyllid and both, after detachment - Mengke Yang; Jianling Li; Haili Qiao; Kun Guo; Rong Xu; Hongshuang Wei; Jianhe Wei; Sai Liu; Changqing Xu (Experimental and Applied Acarology, 2023)

Study on electrothermal ignition model of self-propagation high-temperature synthesis system for samarium vaporization - Yanshuai Zheng; Kun Xue; Yang Qiu; Zheng-Wen Xu; Hai-Sheng Zhao; Ju-Tao Yang; Shouzhi Xie; Hai-Ying Li (Advances in Space Research, 2023)

Recent advances in research on Allium plants: functional ingredients, physiological activities, and applications in agricultural and food sciences - Jing-Kun Yan; Jie Zhu; Yujia Liu; Xu Chen; Wenhan Wang; Henan Zhang; Lin Li (Critical Reviews in Food Science and Nutrition, 2023)

Coupling of soil methane emissions at different depths under typical coastal wetland vegetation types - Kun Li; Zihao Wang; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xiaoyan Shen; Xiaoya Xu; Qingfeng Chen (Chemosphere, 2023)

Enhanced removal of antibiotic and antibiotic resistance genes by coupling biofilm electrode reactor and manganese ore substrate up-flow microbial fuel cell constructed wetland system - Hua Li; Kun Wang; Jiale Xu; Huifang Wu; YuanJiXiang Ma; Rusen Zou; Hai-Liang Song (Chemosphere, 2023)

Crystallization-driven evolution of water occurrence states with implications on dewaterability improvement of waste-activated sludge - Boran Wu; Hewei Li; Kun Zhou; Ningrui Yu; Qinqin Xu; Xiaoli Chai; Xiaohu Dai (Water Research, 2023)

Flexible unmanned surface vehicles control using probabilistic model-based reinforcement learning with hierarchical Gaussian distribution - Yunduan Cui; Kun Xu; Chunhua Zheng; Jia Liu; Lei Peng; Huiyun Li (Ocean Engineering, 2023)

Soil moisture at 30 m from multiple satellite datasets fused by random forest - Jing Ning; Yunjun Yao; Qingxin Tang; Yufu Li; Joshua B. Fisher; Xiaotong Zhang; Kun Jia; Jia Xu; Ke Shang; Junming Yang; Ruiyang Yu; Lu Liu; et al. (Journal of Hydrology, 2023)

Cadmium accumulation in paddy soils affected by geological weathering and mining: Spatial distribution patterns, bioaccumulation prediction, and safe land usage - Cheng Li; Zhongfang Yang; Tao Yu; Zhongcheng Jiang; Qibo Huang; Yeyu Yang; Xu Liu; Xudong Ma; Bo Li; Kun Lin; Tengfang Li (Journal of Hazardous Materials, 2023)

CaHMA1 promotes Cd accumulation in pepper fruit - Weihong Xu; He Huang; Xiaodong Li; Mei Yang; Sunlin Chi; Yu Pan; Nannan Li; Andrew H. Paterson; Yourong Chai; Kun Lu (Journal of Hazardous Materials, 2023)

Lipid metabolic links between serum pyrethroid levels and the risk of incident type 2 diabetes: A mediation study in the prospective design - Chengyong Jia; Gaokun Qiu; Hao Wang; Shiyang Zhang; Jun An; Xu Cheng; Peiwen Li; Wending Li; Xin Zhang; Handong Yang; Kun Yang; Tao Jing; et al. (Journal of Hazardous Materials, 2023)

Experimental and numerical investigation of seismic performance of prefabricated double-column piers used in accelerated bridge construction - Guangda Zhang; Sibo Su; Qiang Han; Kun Xu; Zhipeng Li; Xiuli Du (Engineering Structures, 2023)

A novel lever-arm tuned mass damper inerter (LTMDI) for vibration control of long-span bridges - Zhenchuan Li; Kun Xu; Ruisheng Ma; Kaiming Bi; Qiang Han (Engineering Structures, 2023)

Parameter analysis and design on socket CFST column-cap beam joint with UHPC grouted connection - Guangda Zhang; Qiang Han; Kun Xu; Yanchen Song; Zhipeng Li; Xiuli Du (Engineering Structures, 2023)

Risk assessment of coal mine gas explosion based on cloud integrated similarity and fuzzy DEMATEL - Kun Xu; Shuang Li; Cheng Lu; Jiao Liu (Process Safety and Environmental Protection, 2023)

Structure and anti-inflammatory activity of neo-clerodane diterpenoids from Scutellaria barbata - ShuTing Li; Dan Xu; Jing Jia; Wenbo Zou; JieYing Liu; Yao Wang; Kun Zhang; Xi Zheng; Yan-Yan Ma; Xuejian Zhang; Deng-Gao Zhao (Phytochemistry, 2023)

PxRdl2 dsRNA increased the insecticidal activities of GABAR-targeting compounds against Plutella xylostella - Ben-Jie Li; Kun-Kun Wang; Ye Yu; Jia-Qi Wei; Jian Zhu; Jia-Li Wang; Fei Lin; Han-Hong Xu (Pesticide Biochemistry and Physiology, 2023)

Geochemical characteristics of the Chang 7 Member in the southwestern Ordos Basin, China: the influence of sedimentary environment on the organic matter enrichment - Chen Li; Shi-Jia Chen; Jian-Bo Liao; Yu-Ting Hou; Jian Yu; Guang-Lin Liu; Kun Xu; Xue-Ting Wu (Palaeoworld, 2023)

Surface chemistry engineering enables polar solvent resistant and highly emissive perovskite nanocrystals for multifunctional applications - Dejian Chen; Kunyuan Xu; Mingwei Yang; Jie Hu; Renfu Li; Decai Huang; Sisi Liang; Kun He; Linfeng Yuan; Shujian Wang; Cong Zhou; Jiaxuan Zhang; et al. (Chemical Engineering Journal, 2023)

Catechol-chitosan/carboxymethylated cotton-based Janus hemostatic patch for rapid hemostasis in coagulopathy - Qian Xu; Enling Hu; Haoyu Qiu; Lu Liu; Qing Li; Bitao Lu; Kun Yu; Fei Lu; Ruiqi Xie; Guangqian Lan; Yuansong Zhang (Carbohydrate Polymers, 2023)

Fluoride contents in commonly used commercial phosphate fertilizers and their potential risks in China - Hao Li; Xuzhe Ma; Xunrong Huang; Wei Ji; Kun Chen; Shaoquan Xu; Pengcheng Gao (Environmental Monitoring and Assessment, 2023)

Enhancement of electrokinetic-phytoremediation by Ophiopogon japonicus: stimulation of electrokinetic on root system and improvement of polycyclic aromatic hydrocarbon degradation - Ming Li; Yingping Huang; Kun Li; Xi Yuan; Huigang Liu; Meng Li; Tao Xu; Zhaonian Zhang; David M. Johnson; Ying Xi (Environmental Science and Pollution Research, 2023)

A sustainable and low pollutive strategy for the recycling of waste hot-gas filter bags: The development of filter reinforced epoxy composites - Weisi Fan; Pengxian Hui; Wenjuan Tu; Yuan Li; Hui Xu; Guanchen Zhou; Kun Zhang; Wanshuang Liu; Qiuran Jiang (Waste Management, 2023)

Sustained-release nitrate combined with microbial fuel cell: A novel strategy for PAHs and odor removal from sediment - Lili Chen; Xiangjian Zheng; Kun Zhang; Baile Wu; Xu Pei; Weisong Chen; Xiaoli Wei; Zifeng Luo; Yongtao Li; Zhen Zhang (Journal of Hazardous Materials, 2023)

County-level and monthly resolution multi-pollutant emission inventory for residential solid fuel burning in Fenwei Plain, China - Bin Zhang; Zhenxing Shen; Jian Sun; Leiming Zhang; Kun He; Yue Zhang; Hongmei Xu; Jing Lv; Lei Cao; Jianjun Li; Suixin Liu; Junji Cao (Environmental Pollution, 2023)

Theoretical study of supported ionic liquid membrane reaction and transport for CO2 cycloaddition reaction - Jian-Fei Sun; Xu-Peng Chen; Xin-Tong Li; Kun-Peng Yu; Qin-Qin Xu; Jin-Tao Wu; Lin Li; Jian-Zhong Yin (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Identification of Immune-Linked Hub Genes and Diagnostic Model Construction in Schizophrenia - Kun Lian; Zonglin Shen; Runxu Yang; Jing Ye; Binli Shang; Lei Dong; Hongfang Li; Jiabing Wu; Yuqi Cheng; Xiufeng Xu (Journal of Molecular Neuroscience, 2023)
Schizophrenia (SCZ) is a prevalent, severe, and persistent mental disorder with an unknown etiology. Growing evidence indicates that immunological dysfunction is vital in the development of SCZ. Our study aims to uncover potential immune-linked hub genes and immune infiltration characteristics of SCZ, as well as to develop a diagnostic model based on immune-linked central genes. GSE38484 and GSE54913 chip expression data for patients with SCZ and healthy controls were retrieved. Weighted gene co-expression network analysis (WGCNA) was performed to identify major module genes and critical immune-linked genes. Functional enrichment analysis was conducted to elucidate the involvement of key genes in the immunological response to SCZ, along with the examination of their protein interactions. Moreover, 202 peripheral blood samples were examined using the single-sample gene set enrichment analysis (ssGSEA) method to detect distinct immune cell types. Hub immune-linked genes in SCZ were identified using the minimal absolute contraction and selection operator analysis. Receptor profiles of central immune-linked genes were analyzed to distinguish the two groups. Finally, the association between immune-linked hub genes and various types of immune cells was assessed. Our findings revealed ten immune cell types and nine key genes involved in SCZ, including effector memory CD4+ T cells, activated CD8+ T cells, mast cells, naive CD8+ T cells, PBMC, type 17 helper cells (Th17), central memory CD8+ T cells, CD56 bright NK cells, memory B cells, and regulatory T cells. Diagnostic models constructed using LASSO regression exhibited an average area under the curve (AUC) of 0.866. Our results indicate immunological dysfunction as a factor in the development of SCZ. ASGR2 , ADRM1 , AHANK , S100A8 , FUCA1 , AKNA , GATA3 , AHCYL2 , and PTRH2 are the key regulatory genes of immune cells, highlighting their potential as novel therapeutic targets for SCZ.

The histone acetyltransferase Mof regulates Runx2 and Osterix for osteoblast differentiation - Jianmei Chen; Di Liu; Bo Chen; Yang Yang; Hongying Zhu; Danyang Li; Kun Liu; Lina Zhu; Hongrui Liu; Minqi Li; Xu Zhang; Xiangzhi Li (Cell and Tissue Research, 2023)

A novel fluorescent probe for imaging endogenous hydrogen sulfide in living cells and mice models of acute liver injury - Kai Wang; Rui Guo; Xu-Yang Chen; Xiu-Lin Li; Zhi-Gang Hu; Xiao Wang; Chao-Yue Wang; Ya-Juan Qin; Kun Yao; Yu-Shun Yang (Chemical Engineering Journal, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Identification of the spatial patterns and controlling factors of Se in soil and rice in Guangxi through hot spot analysis - Xu Liu; Chaosheng Zhang; Tao Yu; Wenbing Ji; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Bo Li; Lei Wang; Yuxiang Shao; Kun Lin; Xudong Ma; et al. (Environmental Geochemistry and Health, 2023)

Mechanical characteristics of failure and rockburst proneness of fractured granite from Shuangjiangkou hydropower station under triaxial loading and unloading - Hangli Gong; Yi Luo; Kun Xu; Xuyi Wang; Yuhang Tao; Xinping Li (Bulletin of Engineering Geology and the Environment, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

Identification of soil parent materials in naturally high background areas based on machine learning - Cheng Li; Chaosheng Zhang; Tao Yu; Xudong Ma; Yeyu Yang; Xu Liu; Qingye Hou; Bo Li; Kun Lin; Zhongfang Yang; Lei Wang (Science of The Total Environment, 2023)

Stelleratenoids A−F, macrocyclic daphnane orthoesters with anti-HIV activity from the roots of Stellera chamaejasme L. - Kang Ding; Zi-Yao Wu; Nuan Zhang; Jun He; Fan Zhang; Jing-Jing Wu; Hong-Jin Bai; Wei-Ku Zhang; Lin Li; Jie-Kun Xu (Phytochemistry, 2023)

Anti-inflammatory activity of phenolics from Hypericum japonicum - Xinyu Li; Dan Xu; JieYing Liu; Yan-Yan Ma; Deng-Gao Zhao; Kun Zhang (Phytochemistry Letters, 2023)

Heterogeneous photo-Fenton degradation of acid orange 7 activated by red mud biochar under visible light irradiation - Kun Lin; Shahzad Afzal; Liheng Xu; Tao Ding; Feng Li; Ming Zhang (Environmental Pollution, 2023)

Discovery of seven-membered ring berberine analogues as highly potent and specific hCES2A inhibitors - Yun Yang; Yuan Xiong; Guanghao Zhu; Mengru Sun; Kun Zou; Yitian Zhao; Yong Zhang; Zhijian Xu; Yiming Li; Weiliang Zhu; Qi Jia; Bo Li; et al. (Chemico-Biological Interactions, 2023)

MiR-124-3p inhibits tumor progression in prostate cancer by targeting EZH2 - Bao-feng Song; Li-zhe Xu; Kun Jiang; Fan Cheng (Functional & Integrative Genomics, 2023)
Prostate cancer (PCa) is widespread cancer with significant morbidity and mortality rates. MicroRNAs (miRNAs) have been identified as important post-transcriptional modulators in various malignancies. This study investigated the miR-124-3p effect on PCa cell proliferation, infiltration, and apoptosis. EZH2 and miR-124-3p expression levels were measured in PCa tissues. PCa cell lines DU145 and PC3 were transfected with miR-124-3p inhibitors or analogs. EZH2 and miR-124-3p linkage was validated by conducting the luciferase enzyme reporter test. The cell viability and apoptosis were assessed by flow cytometry and MTT test. Cell movement was noted during infiltration using transwell assays. EZH2, AKT, and mTOR contents were assessed using qRT-PCR and western blotting. In clinical PCa specimens, miR-124-3p and EZH2 contents were inversely correlated. Further research has demonstrated that EZH2 is the miR-124-3p direct target. Furthermore, miR-124-3p overexpression reduced EZH2 levels and lowered cell viability, infiltration, and promoted cell death, whereas miR-124-3p silencing had the opposite effect. Overexpression of miR-124-3p decreased the phosphorylation level of AKT and mTOR, whereas miR-124-3p downregulation produced the opposite result. Our findings depict that miR-124-3p prevents PCa proliferative and invasive processes while promoting apoptosis by targeting EZH2.

Critical thresholds for stage division of water erosion process in different ridge systems in mollisol region of Northeast China - Jian Jiao; Wei Qin; Kun-heng Li; Hai-chao Xu; Zhe Yin; Shu-yan Hou (Journal of Mountain Science, 2023)

Multiple Episodes of Zircon Growth during Anatectic Metamorphism of Metasedimentary Rocks in Collisional Orogens: Constraints from Felsic Granulites in the Bohemian Massif - Guang Yang; Ren-Xu Chen; Yong-Fei Zheng; Qiong-Xia Xia; Yong-Jie Yu; Kun Li; Zhaochu Hu; Bing Gong; Xiang-Ping Zha (Journal of Earth Science, 2023)

Numerical simulation of the electromagnetic field in layered media applicable to high-frequency scenarios - Kun Li; Xu-Ri Huang; Kang Chen; Yun-Gui Xu; Wei-Ping Cao (Applied Geophysics, 2023)

Drinking water quality and inflammatory bowel disease: a prospective cohort study - Shuduo Zhou; Pengfei Chai; Xuejie Dong; Zhisheng Liang; Zongming Yang; Junxia Li; Guigen Teng; Shengzhi Sun; Ming Xu; Zhi-Jie Zheng; Jianbing Wang; Zhenyu Zhang; et al. (Environmental Science and Pollution Research, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

Impact of progressively cumulative exposure of AgNPs on earthworms (Eisenia fetida) and implication for eco-toxicological risk assessment - Caide Huang; Xu Feng; Shizhong Yue; Li Jia; Kun Wang; Wenhao Zhou; Yuhui Qiao (Chemosphere, 2023)

Effects of saline-alkali stress on the tissue structure, antioxidation, immunocompetence and metabolomics of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Science of The Total Environment, 2023)

Identification, in silico selection, and mechanism study of novel antioxidant peptides derived from the rice bran protein hydrolysates - Li-kun Ren; Jing Fan; Yang Yang; Xiao-fei Liu; Bing Wang; Xin Bian; Dang-feng Wang; Yue Xu; Bao-xiang Liu; Peng-yu Zhu; Na Zhang (Food Chemistry, 2023)

Multi-scale structure characterization of ozone oxidized waxy rice starch - Jing Li; Meng Du; Zia-ud Din; Ping Xu; Lei Chen; Xi Chen; Yuehui Wang; Yang Cao; Kun Zhuang; Jie Cai; Qingyun Lyu; Xianhui Chang; et al. (Carbohydrate Polymers, 2023)

Under-loaded operation of an anaerobic-anoxic-aerobic system in dry and wet weather dynamics to prevent overflow pollution: Impacts on process performance and microbial community - Lu-Man Jiang; Zhenjian Zhang; Yunhui Li; Jialei Xu; Kun Wang; Xinya Ding; Junli He; Zhan Qiu; Hua Zhou; Zhen Zhou (Bioresource Technology, 2023)

High-resolution mapping of SrTm4, a recessive resistance gene to wheat stem rust - Hongna Li; Jing Luo; Wenjun Zhang; Lei Hua; Kun Li; Jian Wang; Binyang Xu; Chen Yang; Guiping Wang; Matthew N. Rouse; Jorge Dubcovsky; Shisheng Chen (Theoretical and Applied Genetics, 2023)
Key message The diploid wheat recessive stem rust resistance gene SrTm4 was fine-mapped to a 754-kb region on chromosome arm 2A m L and potential candidate genes were identified. Abstract Race Ug99 of Puccinia graminis f. sp. tritici ( Pgt ), the causal agent of wheat stem (or black) rust is one of the most serious threats to global wheat production. The identification, mapping, and deployment of effective stem rust resistance ( Sr ) genes are critical to reduce this threat. In this study, we generated SrTm4 monogenic lines and found that this gene confers resistance to North American and Chinese Pgt races. Using a large mapping population (9522 gametes), we mapped SrTm4 within a 0.06 cM interval flanked by marker loci CS4211 and 130K1519 , which corresponds to a 1.0-Mb region in the Chinese Spring reference genome v2.1. A physical map of the SrTm4 region was constructed with 11 overlapping BACs from the resistant Triticum monococcum PI 306540. Comparison of the 754-kb physical map with the genomic sequence of Chinese Spring and a discontinuous BAC sequence of DV92 revealed a 593-kb chromosomal inversion in PI 306540. Within the candidate region, we identified an L-type lectin-domain containing receptor kinase ( LLK1 ), which was disrupted by the proximal inversion breakpoint, as a potential candidate gene. Two diagnostic dominant markers were developed to detect the inversion breakpoints. In a survey of T. monococcum accessions, we identified 10 domesticated T. monococcum subsp. monococcum genotypes, mainly from the Balkans, carrying the inversion and showing similar mesothetic resistant infection types against Pgt races. The high-density map and tightly linked molecular markers developed in this study are useful tools to accelerate the deployment of SrTm4 -mediated resistance in wheat breeding programs.

Advances and challenges in interaction between heteroglycans and Bifidobacterium: Utilization strategies, intestinal health and future perspectives - Long-Qing Li; Xu Chen; Jie Zhu; Shuyan Zhang; Si-Qian Chen; Xiaozhen Liu; Lin Li; Jing-Kun Yan (Trends in Food Science & Technology, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Emergence of superconducting dome in ZrN films via variation of nitrogen concentration - Fucong Chen; Xinbo Bai; Yuxin Wang; Tao Dong; Jinan Shi; Yanmin Zhang; Xiaomin Sun; Zhongxu Wei; Mingyang Qin; Jie Yuan; Qihong Chen; Xinbo Wang; et al. (Science Bulletin, 2023)

Attenuation of tetracyclines and related resistance genes in soil when exposed to nanoscale zero-valent iron - Xu Li; Huijie Lu; Kun Yang; Lizhong Zhu (Journal of Hazardous Materials, 2023)

Novel antioxidant peptide from broken rice resist H2O2-induced premature senescence in 2BS cells via PI3K/Akt and JNK/Bax signaling pathway - Li-kun Ren; Yang Yang; Jing Fan; Chun-min Ma; Xin Bian; Dang-feng Wang; Yue Xu; Bao-xiang Liu; Na Zhang (Food Bioscience, 2023)

Inhibition of human sulfotransferases (SULTs) by per- and polyfluoroalkyl substances (PFASs) and structure-activity relationship - Yong-Zhe Liu; Kai Yang; Wei Zhang; Qian zhang; Tong-Feng Liu; Tong Xu; Yang Li; Rui-Xue Ran; Kun Yang; Yun-Feng Cao; Zhong-Ze Fang (Food and Chemical Toxicology, 2023)

Ganoderma lucidum extract promotes tumor cell pyroptosis and inhibits metastasis in breast cancer - Chunlian Zhong; Yumei Li; Wulin Li; Shu lian; Ye Li; Changhui Wu; Kun Zhang; Guiyu Zhou; Weiyu Wang; Huo Xu; Mingqing Huang; Vladimir Katanaev; et al. (Food and Chemical Toxicology, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

VOC emission profiles from typical solid fuel combustion in Fenhe River Basin: Field measurements and environmental implication - Qin Peng; Lizhen Li; Jian Sun; Kun He; Bin Zhang; Haijiang Zou; Hongmei Xu; Junji Cao; Zhenxing Shen (Environmental Pollution, 2023)

Numerical analysis and design method of UHPC grouted RC column- footing socket joints - Guangda Zhang; Qiang Han; Kun Xu; Yanchen Song; Jianglong Li; Weili He (Engineering Structures, 2023)

Bioinspired heterogeneous and hierarchical porous structure of oxo-graphene assembly for spontaneous energy harvesting from air - Kun Fan; Mingjie Peng; Jiaxiang Liu; Xin Li; Xu Wang; Biao Kong; Xiangyang Liu (Chemical Engineering Journal, 2023)

Bufalin reverses cancer-associated fibroblast-mediated colorectal cancer metastasis by inhibiting the STAT3 signaling pathway - Haijing Wang; Jinbao Chen; Sen Li; Jiahua Yang; Donghao Tang; Wentao Wu; Kun Yu; Yijun Cao; Ke Xu; Peihao Yin; Yi Chen; Wei Li (Apoptosis, 2023)

Physicochemical, structural, and rheological characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Lichao Zhao; Luobang Wu; Longqing Li; Jie Zhu; Xu Chen; Shuyan Zhang; Lin Li; Jing-Kun Yan (Food Hydrocolloids, 2023)

Changes in structure and physicochemical properties of Sophora japonica f. pendula galactomannan in late growth stage - Wei Xu; Minghui Han; Yantao Liu; Yana Zhu; Fenglun Zhang; Fuhou Lei; Kun Wang; Li Ji; Jianxin Jiang (Carbohydrate Polymers, 2023)

First evaluation of GPM-Era satellite precipitation products with new observations on the western Tibetan Plateau - Changhui Zhan; Yingying Chen; Kun Yang; Lazhu; Xu Zhou; Yaozhi Jiang; Xiaoyan Ling; Jiaxin Tian; Yan Wang; Xin Li; Hua Yang (Atmospheric Research, 2023)

Research on the Purification Performance of a Floating Island System Treating the Effluent of WWTP Under Different Seasons - Zhao-xu Peng; Ning-qi Niu; Ting-mei Li; Lu-ji Yu; Li-kun Gu; Ming-hui Liu (Water, Air, & Soil Pollution, 2023)

Integrated dual-channel electrochemical immunosensor for early diagnosis and monitoring of periodontitis by detecting multiple biomarkers in saliva - Wei Zhang; Juanrui Du; Kun Wang; Yige Li; Cong Chen; Long Yang; Zitong Kan; Biao Dong; Lin Wang; Lin Xu (Analytica Chimica Acta, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

Exploring global attention mechanism on fault detection and diagnosis for complex engineering processes - Kun Zhou; Yifan Tong; Xintong Li; Xiaoran Wei; Hao Huang; Kai Song; Xu Chen (Process Safety and Environmental Protection, 2023)

Hyperforin: A natural lead compound with multiple pharmacological activities - Xin-Xin Li; Yu Yan; Jia Zhang; Kang Ding; Cong-Yuan Xia; Xue-Ge Pan; Yan-Jing Shi; Jie-Kun Xu; Jun He; Wei-Ku Zhang (Phytochemistry, 2023)

Synergetic effect of Ce/Zr for ethanol synthesis from syngas over Rh-based catalyst - Caixia Zhu; Kaizhuang Xu; Yuan Fang; Qian Lv; Kun Jiang; Huibo Zhao; Yang Chen; Peng Wang; Hua Yang; Lizhi Wu; Yu Tang; Li Tan (Fuel, 2023)

Preparation of N-doped cellulose-based hydrothermal carbon using a two-step hydrothermal induction assembly method for the efficient removal of Cr(VI) from wastewater - Xinkun Zhao; Hongxu Liang; Zihao Wang; Daijia Li; Xiaoyan Shen; Xiaoya Xu; Kun Li; Qingyue Xiang; Yihan Wu; Qingfeng Chen (Environmental Research, 2023)

Precision nitrogen management regimes to obtain high yield and good eating quality of medium indica hybrid rice in mechanical transplanting with bowl-type nursery tray (MTB) based on the critical nitrogen concentration - Haibing He; Kun Yang; Haochong Xu; Bo Yao; Ganghua Li; Xuenan Zhang; Ru Yang; Cuicui You; Jian Ke; Liquan Wu (European Journal of Agronomy, 2023)

Bioactive hydrogel encapsulated dual-gene engineered nucleus pulposus stem cells towards intervertebral disc tissue repair - Yuchen Ye; Panpan Xu; Cai Li; Shichang Jin; Jie Hu; Yuekun Fang; Kun Zhu; Gang Xu; Zhongbing Han; Zhili Zhang; Nan Wu; Pan Jiang; et al. (Chemical Engineering Journal, 2023)

Ionic crosslinking of alginate/carboxymethyl chitosan fluorescent hydrogel for bacterial detection and sterilization - Kun Yan; Yekai Wan; Feiyang Xu; Jing Lu; Chenguang Yang; Xiufang Li; Zhentan Lu; Xungai Wang; Dong Wang (Carbohydrate Polymers, 2023)

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling - Yan Li; Ru Xu; Kun Yang; Yanxu Liu; Shuai Wang; Sha Zhou; Zhao Yang; Xiaoming Feng; Chunyang He; Zhengjie Xu; Wenwu Zhao (Global Change Biology, 2023)
The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP ecosystems for their contribution to precipitation. We found TP ecosystems contributed substantially to local and downwind precipitation, with a contribution of 221 mm/year for the TP and neighboring areas through evapotranspiration (ET) (104 mm/year through transpiration), declined to

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Soil nitrogen substances and denitrifying communities regulate the anaerobic oxidation of methane in wetlands of Yellow River Delta, China - Zihao Wang; Kun Li; Xiaoyan Shen; Feifei Yan; Xinkun Zhao; Yu Xin; Linhui Ji; Qingyue Xiang; Xinyi Xu; Daijia Li; Junhao Ran; Xiaoya Xu; et al. (Science of The Total Environment, 2023)

Charge instability of topological Fermi arcs in chiral crystal CoSi - Zhicheng Rao; Quanxin Hu; Shangjie Tian; Qing Qu; Congrun Chen; Shunye Gao; Zhenyu Yuan; Cenyao Tang; Wenhui Fan; Jierui Huang; Yaobo Huang; Li Wang; et al. (Science Bulletin, 2023)

Meeting China’s electricity demand with renewable energy over Tibetan Plateau - Wenjun Tang; Shan Xu; Xu Zhou; Kun Yang; Yang Wang; Jun Qin; Haikun Wang; Xin Li (Science Bulletin, 2023)

Numerical simulation of microchannel flow boiling and critical heat flux under rolling motion - Zhen Tian; Kun Li; Yuan Zhang; Zhikang Huang; Shuming Xu; Wenzhong Gao (International Journal of Refrigeration, 2023)

Magnetically-separable cobalt catalyst embedded in metal nitrate-promoted hierarchically porous N-doped carbon nanospheres for hydrodeoxygenation of lignin-derived species - Haitao Yu; Yang Xu; Meng Zhang; Li Zhang; Wenjin Wu; Kun Huang (Fuel, 2023)

A pectic polysaccharide from fresh okra (Abelmoschus esculentus L.) beneficially ameliorates CCl4-induced acute liver injury in mice by antioxidation, inhibition of inflammation and modulation of gut microbiota - Jing-Kun Yan; Chun Wang; Ting-Ting Chen; Jie Zhu; Xu Chen; Longqing Li; Xiaozhen Liu; Henan Zhang; Lin Li (Food and Chemical Toxicology, 2023)

Metabolomics analysis reveals the response mechanism to carbonate alkalinity toxicity in the gills of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

MOF-818 nanozyme-based colorimetric and electrochemical dual-mode smartphone sensing platform for in situ detection of H2O2 and H2S released from living cells - Kun Yu; Mengjie Li; Huining Chai; Qian Liu; Xin Hai; Mingwei Tian; Lijun Qu; Tailin Xu; Guangyao Zhang; Xueji Zhang (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Mechanisms of cancer cell killing by metformin: a review on different cell death pathways - Xiao-yu Wu; Wen-Wen Xu; Xiang-kun Huan; Guan-nan Wu; Gang Li; Yu-Hong Zhou; Masoud Najafi (Molecular and Cellular Biochemistry, 2023)

Comprehensive insights into the influence of supplemental green light on the photosynthesis of ginger (Zingiber officinale Roscoe) - Xue Lv; Song Gao; Na Li; Yao Lv; Zijing Chen; Bili Cao; Kun Xu (Protoplasma, 2022)

Hedgehog pathway is negatively regulated during the development of Drosophila melanogaster PheRS-m (Drosophila homologs gene of human FARS2) mutants - Lidangzhi Mo; Rui Li; Chunxia He; Qi Chen; Changwei Xu; Liangliang Shen; Kun Chen; Yuanming Wu (Human Cell, 2022)

Phthalate exposure enhances incidence of urinary incontinence: US NHANES, 2003–2004 and 2005–2006 - Xianyanling Yi; Kun Jin; Shi Qiu; Xingyu Xiong; Tianyi Zhang; Ge Peng; Dazhou Liao; Xiaonan Zheng; Hang Xu; Hong Li; Lu Yang; Qiang Wei; et al. (Environmental Science and Pollution Research, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Global air-sea CO2 exchange flux since 1980s: results from CMIP6 Earth System Models - Baoxiao Qu; Jinming Song; Xuegang Li; Huamao Yuan; Kun Zhang; Suqing Xu (Journal of Oceanology and Limnology, 2022)

The effect of meteorological drought on vegetation cover in the Yellow River basin, China - Lu Jia; Kun‐xia Yu; Zhan‐bin Li; Peng Li; Guo‐ce Xu; Yu‐ting Cheng; Xiang Zhang; Zhi Yang (International Journal of Climatology, 2022)
As a widespread natural disaster, drought has a significant impact on changes in regional vegetation cover. Based on 1‐month standardized precipitation index (SPI1), this study took the Yellow River basin (YRB) with frequent droughts as the research object, using NDVI data from 1999 to 2018, Mann–Kendall trend test, and correlation test to study the temporal and spatial characteristics of meteorological drought, explored the response of vegetation cover to meteorological drought, and further discussed the possible factors affecting meteorological drought. The results of the study showed that from 1999 to 2018, the SPI1 in the YRB had not increased significantly in a large area in different months ( p > .05). On the monthly time scale, the NDVI of the YRB gradually increased from north to south, showing a significant increasing trend the central area ( p p p

Multi-omics analysis reveals the mechanism of seed coat color formation in Brassica rapa L. - Huiyan Zhao; Guoxia Shang; Nengwen Yin; Si Chen; Shulin Shen; Haiyan Jiang; Yunshan Tang; Fujun Sun; Yuhan Zhao; Yongchao Niu; Zhi Zhao; Liang Xu; et al. (Theoretical and Applied Genetics, 2022)

Molecular Mechanism of Selenium Affecting the Synthesis of Flavonoids in G. biloba Leaves - Kun Deng; Li Li; Linling Li; Feng Xu; Honghui Yuan; Sanxing Zha; Xian Xiao; Jie Yu; Shuiyuan Cheng; Hua Cheng (Plant Molecular Biology Reporter, 2022)

Building a predictive model to identify clinical indicators for COVID-19 using machine learning method - Xinlei Deng; Han Li; Xin Liao; Zhiqiang Qin; Fan Xu; Samantha Friedman; Gang Ma; Kun Ye; Shao Lin (Medical & Biological Engineering & Computing, 2022)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

Predisposition to atrioventricular septal defects may be caused by SOX7 variants that impair interaction with GATA4 - Baolei Li; Zhuoyan Li; Jianping Yang; Nanchao Hong; Lihui Jin; Yuejuan Xu; Qihua Fu; Kun Sun; Yu Yu; Yanan Lu; Sun Chen (Molecular Genetics and Genomics, 2022)

Hippocampal Activated Microglia May Contribute to Blood–Brain Barrier Impairment and Cognitive Dysfunction in Post-Traumatic Stress Disorder-Like Rats - Kun Ni; Jixiang Zhu; Xuan Xu; Yue Liu; Shuai Yang; Yulin Huang; Rui Xu; Li Jiang; Juan Zhang; Wei Zhang; Zhengliang Ma (Journal of Molecular Neuroscience, 2022)

Toxicity and tissue accumulation characteristics of the herbicide pendimethalin under silicon application in ginger (Zingiber officinale Roscoe) - Yanyan Li; Kai Wang; Yuwen Kong; Yao Lv; Kun Xu (Environmental Science and Pollution Research, 2022)

Experimental research on the mechanical properties and energy transfer of fractured granite under triaxial loading - Yi Luo; Kun Xu; Hangli Gong; Dengxing Qu; Xinping Li; Gang Wang; Qiaoliang Li (Bulletin of Engineering Geology and the Environment, 2022)

Enhanced Intramuscular Bioavailability of Cannabidiol Using Nanocrystals: Formulation, In Vitro Appraisal, and Pharmacokinetics - Xinzhen Fu; Shiji Xu; Zhi Li; Kun Chen; Huaying Fan; Yu Wang; Zeping Xie; Lijuan Kou; Shumin Zhang (AAPS PharmSciTech, 2022)

Global divergent trends of algal blooms detected by satellite during 1982–2018 - Chong Fang; Kaishan Song; Hans W Paerl; Pierre‐Andre Jacinthe; Zhidan Wen; Ge Liu; Hui Tao; Xiaofeng Xu; Tiit Kutser; Zongming Wang; Hongtao Duan; Kun Shi; et al. (Global Change Biology, 2022)
Algal blooms (ABs) in inland lakes have caused adverse ecological effects, and health impairment of animals and humans. We used archived Landsat images to examine ABs in lakes (>1 km 2 ) around the globe over a 37‐year time span (1982–2018). Out of the 176032 lakes with area >1 km 2 detected globally, 863 were impacted by ABs, 708 had sufficiently long records to define a trend, and 66% exhibited increasing trends in frequency ratio (FRQR, ratio of the number of ABs events observed in a year in a given lake to the number of available Landsat images for that lake) or area ratio (AR, ratio of annual maximum area covered by ABs observed in a lake to the surface area of that lake), while 34% showed a decreasing trend. Across North America, an intensification of ABs severity was observed for FRQR ( p p p p

Root morphology ion absorption and antioxidative defense system of two Chinese cabbage cultivars (Brassica rapa L.) reveal the different adaptation mechanisms to salt and alkali stress - Na Li; Bili Cao; Zijing Chen; Kun Xu (Protoplasma, 2022)

A positive response of ginger root zone and rhizome development to suitable sowing depth - Yao Lv; Yanyan Li; Xiaohui Liu; Kun Xu (Protoplasma, 2022)

Caldalkalibacillus salinus sp. nov., isolated from a salt lake in Xinjiang, northwest China - Ting-Hao Ouyang; Man Peng; Zhen Zhang; Wei-Xun Chunyu; Li-Ming Wang; En-Min Zhou; Xu-Hong Gao; Shu-Kun Tang (Archives of Microbiology, 2022)

Geochemical characteristics of source rocks and natural gas in Fudong area, Junggar Basin: implications for the genesis of natural gas - Kun Xu; Shijia Chen; Chaowei Liu; Zhanghao Liu; Chen Li (Arabian Journal of Geosciences, 2022)

Viridibacillus soli sp. nov., isolated from forest soil in Ailaoshan National Nature Reserve - Yan Xu; Jiang-Yuan Zhao; Yu Geng; Hui-Ren Yuan; Le-Le Li; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2022)

Climate change may interact with nitrogen fertilizer management leading to different ammonia loss in China’s croplands - Xiangrui Xu; Xiao Ouyang; Yining Gu; Kun Cheng; Pete Smith; Jianfei Sun; Yunpeng Li; Genxing Pan (Global Change Biology, 2021)
Despite research into the response of ammonia (NH 3 ) volatilization in farmland to various meteorological factors, the potential impact of future climate change on NH 3 volatilization is not fully understood. Based on a database consisting of 1063 observations across China, nonlinear NH 3 models considering crop type, meteorological, soil and management variables were established via four machine learning methods, including support vector machine, multi‐layer perceptron, gradient boosting machine and random forest (RF). The RF model had the highest R 2 of 0.76 and the lowest RMSE of 0.82 kg NH 3 ‐N ha − 1 , showing the best simulation capability. Results of model importance indicated that NH 3 volatilization was mainly controlled by total input of N fertilizer, followed by meteorological factors, human managements and soil characteristics. The NH 3 emissions of China's cereal production (paddy rice, wheat and maize) in 2018 was estimated to be 3.3 Mt NH 3 ‐N. By 2050, NH 3 volatilization will increase by 23.1−32.0% under different climate change scenarios (Representative Concentration Pathways, RCPs), and climate change will have the greatest impact on NH 3 volatilization in the Yangtze river agro‐region of China due to high warming effects. However, the potential increase in NH 3 volatilization under future climate change can be mitigated by 26.1−47.5% through various N fertilizer management optimization options.

Effect of Cyclic Wetting–Drying Treatment on Strength and Failure Behavior of Two Quartz-Rich Sandstones Under Direct Shear - Xiaoshuang Li; Kun Peng; Jun Peng; Hanhua Xu (Rock Mechanics and Rock Engineering, 2021)

Different responses of two Chinese cabbage (Brassica rapa L. ssp. pekinensis) cultivars in photosynthetic characteristics and chloroplast ultrastructure to salt and alkali stress - Na Li; Zhihuan Zhang; Song Gao; Yao Lv; Zijing Chen; Bili Cao; Kun Xu (Planta, 2021)

A network pharmacology study with molecular docking to investigate the possibility of licorice against posttraumatic stress disorder - Zhi-Kun Qiu; Zhi-Ting Liu; Jia-Li Pang; Han-Biao Wu; Xu Liu; Ze-Min Yang; Xiong Li; Ji-Sheng Chen (Metabolic Brain Disease, 2021)

Added value of kilometer-scale modeling over the third pole region: a CORDEX-CPTP pilot study - Xu Zhou; Kun Yang; Lin Ouyang; Yan Wang; Yaozhi Jiang; Xin Li; Deliang Chen; Andreas Prein (Climate Dynamics, 2021)

Optimization of oil source correlation indexes: a case of Chang 10 member in Ordos Basin’ Zhoujiawan area - Kun Xu; Shijia Chen; Yuting Hou; Zixing Lu; Chen Li; Meimei Han (Arabian Journal of Geosciences, 2021)

Grafting improves tomato yield under low nitrogen conditions by enhancing nitrogen metabolism in plants - Zhi Huan Zhang; Ming Ming Li; Bi Li Cao; Zi Jing Chen; Kun Xu (Protoplasma, 2021)

BDNF Participates in Chronic Constriction Injury-Induced Neuropathic Pain via Transcriptionally Activating P2X7 in Primary Sensory Neurons - Yi Wu; Zhiwen Shen; Hui Xu; Kun Zhang; Mingyan Guo; Fei Wang; Junhua Li (Molecular Neurobiology, 2021)

Effects of drought and heat on the productivity and photosynthetic characteristics of alpine meadow plants on the Qinghai-Tibetan Plateau - Li Ma; Zhong-hua Zhang; Bu-qing Yao; Zhen Ma; Xiao-tao Huang; Bing-rong Zhou; Man-hou Xu; Jing Guo; Hua-kun Zhou (Journal of Mountain Science, 2021)

Calcineurin inhibitor–associated new-onset diabetes mellitus in chronic kidney disease treatment: a 4-year single-center cross-sectional study in China - Pan Kun-ming; Chen Can; Xu Qing; Wu Wei; Lv Qian-zhou; Li Xiao-yu (European Journal of Clinical Pharmacology, 2021)

Carbon storage of the forest and its spatial pattern in Tibet, China - Long-yu Jia; Gen-xu Wang; Ji Luo; Fei Ran; Wei Li; Jun Zhou; Dan-li Yang; Wen-bo Shi; Qian Xu; Kun Zhu; Yang Yang (Journal of Mountain Science, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

MiR-124 and Small Molecules Synergistically Regulate the Generation of Neuronal Cells from Rat Cortical Reactive Astrocytes - Yangyang Zheng; Zhehao Huang; Jinying Xu; Kun Hou; Yifei Yu; Shuang Lv; Lin Chen; Yulin Li; Chengshi Quan; Guangfan Chi (Molecular Neurobiology, 2021)

Development and evaluation of a serological test for diagnosis of COVID-19 with selected recombinant spike proteins - Pingping Zhang; Qi Gao; Tang Wang; Yuehua Ke; Fei Mo; Ruizhong Jia; Wanbing Liu; Lei Liu; Shangen Zheng; Yuzhen Liu; Luping Li; Yao Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Pollution characteristics and toxic effects of PM1.0 and PM2.5 in Harbin, China - Guangzhi Wang; Yuanyuan Xu; Likun Huang; Kun Wang; Hairui Shen; Zhe Li (Environmental Science and Pollution Research, 2021)

Down-regulation of MANNANASE7 gene in Brassica napus L. enhances silique dehiscence-resistance - Yu-Long Li; Yan-Kun Yu; Ke-Ming Zhu; Li-Na Ding; Zheng Wang; Yan-Hua Yang; Jun Cao; Li-Zhang Xu; Yao-Ming Li; Xiao-Li Tan (Plant Cell Reports, 2021)

The formation and evolution of parent and oxygenated polycyclic aromatic hydrocarbons during a severe winter haze–fog event over Xi’an, China - Yali Lei; Zhenxing Shen; Kun He; Lijuan Li; Yiming Qin; Yaling Zeng; Jianjun Li; Hongmei Xu; Yongjing Ma; Tian Zhang; Liu Yang; Ningning Zhang; et al. (Environmental Science and Pollution Research, 2021)

Foundation species across a latitudinal gradient in China - Xiujuan Qiao; Jiaxin Zhang; Zhong Wang; Yaozhan Xu; Tianyang Zhou; Xiangcheng Mi; Min Cao; Wanhui Ye; Guangze Jin; Zhanqing Hao; Xugao Wang; Xihua Wang; et al. (Ecology, 2021)
Foundation species structure forest communities and ecosystems but are difficult to identify without long‐term observations or experiments. We used statistical criteria––outliers from size‐frequency distributions and scale‐dependent negative effects on alpha diversity and positive effects on beta diversity––to identify candidate foundation woody plant species in 12 large forest‐dynamics plots spanning 26 degrees of latitude in China. We used these data (1) to identify candidate foundation species in Chinese forests, (2) to test the hypothesis––based on observations of a midlatitude peak in functional trait diversity and high local species richness but few numerically dominant species in tropical forests––that foundation woody plant species are more frequent in temperate than tropical or boreal forests, and (3) to compare these results with data from the Americas to suggest candidate foundation genera in northern hemisphere forests. Using the most stringent criteria, only two species of Acer , the canopy tree Acer ukurunduense and the shrubby treelet Acer barbinerve , were identified in temperate plots as candidate foundation species. Using more relaxed criteria, we identified four times more candidate foundation species in temperate plots (including species of Acer , Pinus , Juglans , Padus , Tilia , Fraxinus , Prunus , Taxus , Ulmus , and Corlyus ) than in (sub)tropical plots (the treelets or shrubs Aporosa yunnanensis , Ficus hispida , Brassaiopsis glomerulata , and Orophea laui ). Species diversity of co‐occurring woody species was negatively associated with basal area of candidate foundation species more frequently at 5‐ and 10‐m spatial grains (scale) than at a 20‐m grain. Conversely, Bray‐Curtis dissimilarity was positively associated with basal area of candidate foundation species more frequently at 5‐m than at 10‐ or 20‐m grains. Both stringent and relaxed criteria supported the hypothesis that foundation species are more common in mid‐latitude temperate forests. Comparisons of candidate foundation species in Chinese and North American forests suggest that Acer be investigated further as a foundation tree genus.

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

Long non-coding RNA HCG18 promotes M1 macrophage polarization through regulating the miR-146a/TRAF6 axis, facilitating the progression of diabetic peripheral neuropathy - Wei Ren; Guangxia Xi; Xing Li; Lingxia Zhao; Kun Yang; Xuemei Fan; Linlin Gao; Hongmei Xu; Jianjin Guo (Molecular and Cellular Biochemistry, 2021)

Failure mode analysis of post-seismic rockfall in shattered mountains exemplified by detailed investigation and numerical modelling - Kun He; Yongjian Li; Guotao Ma; Xiewen Hu; Bo Liu; Zhigang Ma; Zepeng Xu (Landslides, 2021)

Profiles and Source Apportionment of Nonmethane Volatile Organic Compounds in Winter and Summer in Xi’an, China, based on the Hybrid Environmental Receptor Model - Jian Sun; Zhenxing Shen; Yue Zhang; Wenting Dai; Kun He; Hongmei Xu; Zhou Zhang; Long Cui; Xuxiang Li; Yu Huang; Junji Cao (Advances in Atmospheric Sciences, 2021)

OsRbohB-mediated ROS production plays a crucial role in drought stress tolerance of rice - Yi Shi; Yan-Li Chang; Hai-Tao Wu; Abdullah Shalmani; Wen-Ting Liu; Wen-Qiang Li; Jian-Wei Xu; Kun-Ming Chen (Plant Cell Reports, 2020)

Comprehensive analysis of ALK, ROS1 and RET rearrangements in locally advanced rectal cancer - Chunlian Zhou; Min Li; Zhiwei Guo; Kun Li; Xiangming Zhai; Yingchao Xie; Xuexi Yang; Yingsong Wu; Weiwei Xiao; Weiwen Xu (Journal of Genetics, 2020)

Influence of complex topography on magnetotelluric-observed data using three-dimensional numerical simulation: A case from Guangxi area, China - Xiong Bin; Luo Tian-Ya; Chen Long-Wei; Dai Shi-Kun; Xu Zhi-Feng; Li Chang-Wei; Ding Yan-Li; Wang Hong-Hua; Li Jing-He (Applied Geophysics, 2020)

Enhancing the resolution of time–frequency spectrum using directional multichannel matching pursuit - Lu Xu; Xingyao Yin; Kun Li (Acta Geophysica, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Characterizing precipitation in high altitudes of the western Tibetan plateau with a focus on major glacier areas - Duo Li; Kun Yang; Wenjun Tang; Xin Li; Xu Zhou; Donglin Guo (International Journal of Climatology, 2020)
Solid water resources such as glaciers and snow cover are widely distributed in the western Tibetan plateau (WTP), and precipitation is the key supply of them. However, the characteristics of precipitation over the WTP remain unclear due to sparse observations. Using observation‐based gridded data (APHRODITE, GPCC), satellite products (TRMM, GPM), reanalysis data (ERA5, ERA‐Interim, JRA‐55) and weather research and forecasting model (WRF)‐simulation data (HAR10, HAR30), this study investigated the precipitation characteristics in high mountain areas (altitude >2,500 m a.s.l.) of the WTP (26–44°N, 70–85°E) from 2001 to 2013. Results show that annual GPM precipitation (336 mm) is much lower than that of other data sets (570–800 mm) for the WTP and appears to be an outlier; meanwhile, the other data sets show increasing precipitation as grid resolution decreases (becomes coarser). In contrast, high spatial resolution WRF simulations (HAR10, HAR30) yielded considerably higher precipitation in four strongly glacierized alpine areas (Western Himalaya, Karakorum, Tajikistan, and west Kunlun) than the other data sets. When compared to precipitation estimated using the water balance in nine glacierized catchments of the Upper Indus River Basin, the HAR data sets more reasonably represent the amount of precipitation in high mountain areas than the other data sets. The surface albedo, snow cover extent, and snow cover duration observed by satellites further indicate that the HAR data sets yield reasonable spatial variability of precipitation. This implies that the commonly used data sets (such as observation data and satellite products) underestimate the precipitation in high mountain areas. According to the HAR10 data, the four major glacierized areas on the WTP have similar precipitation amounts in summer and autumn, and the winter–spring contribution to annual precipitation is at least 70% in three of these areas (Western Himalaya, Karakorum, and Tajikistan). This pattern indicates that precipitation over the high‐altitude areas in WTP is mainly controlled by the mid‐latitude westerlies. The annual precipitation in these areas is over 1,000 mm, which is comparable to that of the southeast TP but much larger than that on the central plateau. Therefore, the spatial precipitation pattern across the TP is ‘wet east and west, dry middle’.

Prevalence of Autism Spectrum Disorder in China: A Nationwide Multi-center Population-based Study Among Children Aged 6 to 12 Years - Hao Zhou; Xiu Xu; Weili Yan; Xiaobing Zou; Lijie Wu; Xuerong Luo; Tingyu Li; Yi Huang; Hongyan Guan; Xiang Chen; Meng Mao; Kun Xia; et al. (Neuroscience Bulletin, 2020)

Relative pollen productivities of the major plant taxa of subtropical evergreen–deciduous mixed woodland in China - Fangyuan Jiang; Qinghai Xu; Shengrui Zhang; Furong Li; Kun Zhang; Meng Wang; Wei Shen; Yuanhao Sun; Zhongze Zhou (Journal of Quaternary Science, 2020)
Quantifying the relationship between pollen and vegetation is an essential step in the pollen‐based quantitative reconstruction of past vegetation cover. In this study, we use the Extended R‐Value (ERV) model and a modern dataset of pollen (collected from moss polsters) and related vegetation from 50 sites in the Daba Mountains (subtropical China) to (i) estimate the relevant source area of pollen (RSAP) of the moss samples and the relative pollen productivities (RPPs) of nine major plant taxa‐characteristic of the region, and (ii) evaluate the obtained RPPs. The RSAP estimates of moss polsters vary between 225 and 610 m depending on the ERV submodels and models of pollen dispersal and deposition used. The RPP estimates are different from values published in previous studies from temperate and subtropical China. This may be explained by differences in methodology, climate and vegetation (species composition and spatial distribution), of which vegetation is probably the most important factor. The ranking of the RPP estimates for the nine taxa is Pinus > Juglandaceae > D − Quercus (deciduous Quercus ) > Poaceae > Rosaceae > Cyperaceae > Anacardiaceae > Castanea > Fabaceae. We use a ‘leave‐one‐out’ cross‐validation strategy and the Landscape Reconstruction Algorithm (LRA) for pollen‐based reconstruction of regional and local plant cover to evaluate the ERV model‐based RPP estimates. Both the REVEALS (Regional Estimates of VEgetation Abundance from Large Sites)‐based and the LOVE (LOcal Vegetation Estimates)‐based plant cover using the RPP estimates are closer to the modern vegetation composition than pollen percentages, thus confirming the applicability of the ERV model and the LRA approach in subtropical China.

Comparative transcriptomic analysis of vascular endothelial cells after hypoxia/re-oxygenation induction based on microarray technology - Jia Xu; Jiu-kun Jiang; Xiao-lin Li; Xiao-peng Yu; Ying-ge Xu; Yuan-qiang Lu (Journal of Zhejiang University-SCIENCE B, 2020)

Numerical simulation of influence of filled joint on the crack formed by notch hole blast - JunHong Huang; XinPing Li; Yi Luo; TingTing Liu; Qian Dong; Kun Xu; ChuXuan Tang (European Journal of Environmental and Civil Engineering, 2020)

Silicon restrains drought-induced ROS accumulation by promoting energy dissipation in leaves of tomato - Bi-li Cao; Qiang Ma; Kun Xu (Protoplasma, 2020)

SIRT3 promotes the invasion and metastasis of cervical cancer cells by regulating fatty acid synthase - Li Xiu Xu; Li Jun Hao; Jun Qi Ma; Jing Kun Liu; Ayshamgul Hasim (Molecular and Cellular Biochemistry, 2020)

Forest community assembly is driven by different strata‐dependent mechanisms along an elevational gradient - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Journal of Biogeography, 2019)
Aim The mechanisms driving forest community assembly along elevational gradients remain elusive. The distinct strata in heterogeneous forest are subject to differing assembly mechanisms. This study aims to evaluate how different ecological mechanisms driving forest community assembly across strata and spatial scales, and to identify how these assemblages respond to different abiotic or biotic variables along an elevational gradient. Location Yulong Mountain within Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We sampled plant species along a 1,200 m elevational gradient across forest strata (trees, shrubs and herbs) at different spatial scales (neighbourhood and community). We integrated phylogenetic and functional diversity to disentangle the roles of ecological mechanisms in structuring community assembly. We also determined the relative effects of climatic, soil and biotic variables and their interactions on these community assemblages. Results The phylogenetic and functional diversity of trees were lower at the extremes of the elevational gradient, where they were constrained by water availability or temperature. While communities with higher species diversity exhibited an overdispersed structure at mid‐elevations. For shrubs, overdispersion was exhibited at high elevations despite low species richness, which could be consistent with facilitative interactions or competition exclusion. However, most communities of herbs appear to have a markedly random structure, despite some incongruence between phylogenetic divergence and functional convergence, as well as influences from overstorey trees and local light conditions. The relative effects of abiotic variables on community structure were larger at the community scale than at the neighbourhood scale. Main conclusions Our study emphasises the importance of considering phylogenies and traits in understanding the strata‐ and scale‐dependent mechanisms of forest community assembly. Collectively, results indicate that contrasting assembly mechanisms interact across different strata along elevational gradients to shape diverse forest communities.

Study of sedimentary characteristic in Denglouku formation, southern Songliao basin, Northeast China - Zhan-dong Li; Peng Wang; Li Li; Wei Li; Jin-ze Xu; Yi-kun Liu (Carbonates and Evaporites, 2019)

Greater than the sum of the parts: how the species composition in different forest strata influence ecosystem function - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Jia‐Yun Zou; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Ecology Letters, 2019)
The mechanisms underpinning forest biodiversity‐ecosystem function relationships remain unresolved. Yet, in heterogeneous forests, ecosystem function of different strata could be associated with traits or evolutionary relationships differently. Here, we integrate phylogenies and traits to evaluate the effects of elevational diversity on above‐ground biomass across forest strata and spatial scales. Community‐weighted means of height and leaf phosphorous concentration and functional diversity in specific leaf area exhibited positive correlations with tree biomass, suggesting that both positive selection effects and complementarity occur. However, high shrub biomass is associated with greater dissimilarity in seed mass and multidimensional trait space, while species richness or phylogenetic diversity is the most important predictor for herbaceous biomass, indicating that species complementarity is especially important for understory function. The strength of diversity‐biomass relationships increases at larger spatial scales. We conclude that strata‐ and scale‐ dependent assessments of community structure and function are needed to fully understand how biodiversity influences ecosystem function.

Correction to: Pro-neurogenic effect of β-asarone on RSC96 Schwann cells in vitro - Fuben Xu; Huayu Wu; Kun Zhang; Peizhen Lv; Li Zheng; Jinmin Zhao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Dynamical impact of parameterized turbulent orographic form drag on the simulation of winter precipitation over the western Tibetan Plateau - Xu Zhou; Kun Yang; Anton Beljaars; Huidong Li; Changgui Lin; Bo Huang; Yan Wang (Climate Dynamics, 2019)

A cross-sectional survey based on blood VOCs, hematological parameters and urine indicators in a population in Jilin, Northeast China - Xiaocui Li; Yuanyuan Guo; Xiuling Song; Yinghua He; Huiwen Zhang; Hao Bao; Xinxin Li; Yushen Liu; Yue Zhai; Juan Wang; Kun Xu; Juan Li (Environmental Geochemistry and Health, 2019)

Antiviral activity of aconite alkaloids from Aconitum carmichaelii Debx - Weiming Xu; Min Zhang; Hongwu Liu; Kun Wei; Ming He; Xiangyang Li; Deyu Hu; Song Yang; Yuguo Zheng (Natural Product Research, 2019)

Two pairs of phenolic enantiomers from the leaves of Eucommia ulmoides Oliver - Jian-Kun Yan; Xu-Liu Shi; Paul Owusu Donkor; Xiu-Mei Gao; Li-Qin Ding; Feng Qiu (Natural Product Research, 2019)

The anxiolytic effects of Bai Le Mian capsule, a traditional Chinese hypnotic in mice - Tian-Xiao Wang; Yu-Er Wu; Wei Xu; Wan-Kun Gong; Jian Ni; Wei-Min Qu; Zhi-Li Huang (Sleep and Biological Rhythms, 2019)

Yield, nitrogen use efficiency and economic benefits of biochar additions to Chinese Flowering Cabbage in Northwest China - Zhan Wang; Yin-kun Li; Wen-zhong Guo; Zhi-gang Xu; Li-chun Wang; Li Ma (Nutrient Cycling in Agroecosystems, 2019)

Development of a fine-resolution atmosphere-wave-ocean coupled forecasting model for the South China Sea and its adjacent seas - Junchuan Sun; Zexun Wei; Tengfei Xu; Meng Sun; Kun Liu; Yongzeng Yang; Li Chen; Hong Zhao; Xunqiang Yin; Weizhong Feng; Zhiyuan Zhang; Yonggang Wang (Acta Oceanologica Sinica, 2019)

Zircon U–Pb ages and Hf isotopic compositions of two types of supracrustal rocks in the Northeastern Sulu UHP terrane: constraints on the surface boundary between South China and North China - Yang Xu; Ming-Ling Yang; Ali Polat; Kun-Guang Yang; Yuan-Ku Meng; Ri-Hui Li; Zhong-Bo Wang (International Geology Review, 2019)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

Gastroprotective effect of araloside A on ethanol- and aspirin-induced gastric ulcer in mice: involvement of H+/K+-ATPase and mitochondrial-mediated signaling pathway - Haibo He; Xiaomei Li; Haili Yu; Shu Zhu; Yumin He; Katsuko Komatsu; Dongyan Guo; Xiaoqin Li; Junzhi Wang; Huajun Luo; Daoxiang Xu; Kun Zou (Journal of Natural Medicines, 2019)

Presence of bacteroidales as a predicator of human enteric viruses in Haihe River of Tianjin City, China - Shuqing Zhou; Dong Yang; Qunying Xu; Zhongwei Yang; Min Jin; Jing Yin; Huaran Wang; Kun Zhou; Lianqi Wang; Junwen Li; Zhiqiang Shen (Environmental Science and Pollution Research, 2019)

Static decontamination of oil-based drill cuttings with pressurized hot water using response surface methodology - Zhong Chen; Dongyuan Li; Kun Tong; Zeliang Chen; Hongzhen Chen; Qiao Chen; Yuanjian Xu (Environmental Science and Pollution Research, 2019)

Landslide integrated characteristics and susceptibility assessment in Rongxian county of Guangxi, China - Li-ping Liao; Ying-yan Zhu; Yan-lin Zhao; Hai-tao Wen; Yun-chuan Yang; Li-hua Chen; Shao-kun Ma; Ying-zi Xu (Journal of Mountain Science, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Devonian integrative stratigraphy and timescale of China - Wenkun Qie; Xueping Ma; Honghe Xu; Li Qiao; Kun Liang; Wen Guo; Junjun Song; Bo Chen; Jianfeng Lu (Science China Earth Sciences, 2019)

Laboratory detection and molecular phylogenetic analysis of severe fever with thrombocytopenia syndrome virus in Hubei Province, central China - Bing Hu; Kun Cai; Man Liu; Wenjing Li; Junqiang Xu; Feng Qiu; Jianbo Zhan (Archives of Virology, 2018)

Plant-mediated competition facilitates a phoretic association between a gall mite and a psyllid vector - Jianling Li; Sai Liu; Kun Guo; Fan Zhang; Haili Qiao; Jianmin Chen; Mengke Yang; Xiu Zhu; Rong Xu; Changqing Xu; Jun Chen (Experimental and Applied Acarology, 2018)

Separate Neural Networks for Gains and Losses in Intertemporal Choice - Yang-Yang Zhang; Lijuan Xu; Zhu-Yuan Liang; Kun Wang; Bing Hou; Yuan Zhou; Shu Li; Tianzi Jiang (Neuroscience Bulletin, 2018)

AhR activation protects intestinal epithelial barrier function through regulation of Par-6 - Kun Yu; Yuanhang Ma; Zhicao Zhang; Xin Fan; Teming Li; Liangzi Li; Weidong Xiao; Yujiao Cai; Lihua Sun; Pengyuan Xu; Min Yu; Hua Yang (Journal of Molecular Histology, 2018)

Three-dimensional numerical modeling of gravity anomalies based on Poisson equation in space-wavenumber mixed domain - Shi-Kun Dai; Dong-Dong Zhao; Qian-Jiang Zhang; Kun Li; Qing-Rui Chen; Xu-Long Wang (Applied Geophysics, 2018)

Regulation of myostatin expression is associated with growth and muscle development in commercial broiler and DMC muscle - Tengfei Dou; Zhengtian Li; Kun Wang; Lixian Liu; Hua Rong; Zhiqiang Xu; Ying Huang; Dahai Gu; Xiaobo Chen; Wenyuan Hu; Jiarong Zhang; Sumei Zhao; et al. (Molecular Biology Reports, 2018)

Anxiolytic-like effects of paeoniflorin in an animal model of post traumatic stress disorder - Zhi-Kun Qiu; Jia-Li He; Xu Liu; Jia Zeng; Wei Xiao; Qing-Hong Fan; Xiao-Meng Chai; Wei-Hai Ye; Ji-Sheng Chen (Metabolic Brain Disease, 2018)

PGC-1α coordinates with Bcl-2 to control the cell cycle in U251 cells through reducing ROS - Kun Yao; Xu-feng Fu; Xing Du; Yan Li; Shan-shan Yang; Min Yu; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2018)

Identification and Pathogenicity of Fungal Pathogens Causing Black Point in Wheat on the North China Plain - Kai-Ge Xu; Yu-Mei Jiang; Yang-Kun Li; Qiao-Qiao Xu; Ji-Shan Niu; Xin-Xin Zhu; Qiao-Yun Li (Indian Journal of Microbiology, 2018)

Melatonin Augments the Effects of Fluoxetine on Depression-Like Behavior and Hippocampal BDNF–TrkB Signaling - Kun Li; Si Shen; Yu-Tian Ji; Xu-Yun Li; Li-San Zhang; Xiao-Dong Wang (Neuroscience Bulletin, 2018)

Identification of ZFPM2 mutations in sporadic conotruncal heart defect patients - Tian Pu; Yang Liu; Rang Xu; Fen Li; Sun Chen; Kun Sun (Molecular Genetics and Genomics, 2018)

The anxiolytic-like effects of puerarin are associated with the changes of monoaminergic neurotransmitters and biosynthesis of allopregnanolone in the brain - Zhi-Kun Qiu; De-Sheng Zhong; Jia-Li He; Xu Liu; Ji-Sheng Chen; Hong Nie (Metabolic Brain Disease, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

Silicon-mediated changes in radial hydraulic conductivity and cell wall stability are involved in silicon-induced drought resistance in tomato - Bi-li Cao; Lili Wang; Song Gao; Jie Xia; Kun Xu (Protoplasma, 2017)

IAA producing Bacillus altitudinis alleviates iron stress in Triticum aestivum L. seedling by both bioleaching of iron and up-regulation of genes encoding ferritins - Zhongke Sun; Kun Liu; Ju Zhang; Yi Zhang; Kedong Xu; Deshui Yu; Jian Wang; Lizong Hu; Long Chen; Chengwei Li (Plant and Soil, 2017)

Genetic and transcriptomic analyses of lignin- and lodging-related traits in Brassica napus - Lijuan Wei; Hongju Jian; Kun Lu; Nengwen Yin; Jia Wang; Xiujian Duan; Wei Li; Liezhao Liu; Xinfu Xu; Rui Wang; Andrew H. Paterson; Jiana Li (Theoretical and Applied Genetics, 2017)

AKTs/PKBs: molecular characterization, tissue expression and transcriptional responses to insulin and/or wortmannin in yellow catfish Pelteobagrus fulvidraco - Mei-Qin Zhuo; Ya-Xiong Pan; Kun Wu; Yi-Huan Xu; Li-Han Zhang; Zhi Luo (Fish Physiology and Biochemistry, 2017)

Astragaloside IV, a Natural PPARγ Agonist, Reduces Aβ Production in Alzheimer’s Disease Through Inhibition of BACE1 - Xu Wang; Yue Wang; Jiang-Ping Hu; Song Yu; Bao-Kun Li; Yong Cui; Lu Ren; Li-De Zhang (Molecular Neurobiology, 2017)

Retraction Note to: CXCR4 Signaling Induced Epithelial-Mesenchymal Transition by PI3K/AKT and ERK Pathways in Glioblastoma - Baoyu Lv; Xiangshan Yang; Shunzeng Lv; Lei Wang; Kaixi Fan; Ranran Shi; Fengling Wang; Huishu Song; Xiaochen Ma; Xuefen Tan; Kun Xu; Jingjing Xie; et al. (Molecular Neurobiology, 2017)

IRS1 and IRS2: molecular characterization, tissue expression and transcriptional regulation by insulin in yellow catfish Pelteobagrus fulvidraco - Mei-Qin Zhuo; Ya-Xiong Pan; Kun Wu; Yi-Huan Xu; Li-Han Zhang; Zhi Luo (Fish Physiology and Biochemistry, 2017)

Response to the letter to editor “Cadmium exposure and urinary N-acetyl-β-D-glucosaminidase: a meta-analysis” - Cuixia Liu; Yubiao Li; Chunshui Zhu; Zhaomin Dong; Kun Zhang; Yanbin Zhao; Yilu Xu (Environmental Science and Pollution Research, 2017)

Estrogen-like neuroprotection of isopsoralen against spinal cord injury through estrogen receptor ERα - Xiao-ming Li; Qi Yang; Xu-bo Li; Qiang Cheng; Kun Zhang; Jing Han; Jian-ning Zhao; Gang Liu; Ming-gao Zhao (Metabolic Brain Disease, 2017)

Formaldehyde induces toxicity in mouse bone marrow and hematopoietic stem/progenitor cells and enhances benzene-induced adverse effects - Chenxi Wei; Huaxiao Wen; Langyue Yuan; Cliona M. McHale; Hui Li; Kun Wang; Junlin Yuan; Xu Yang; Luoping Zhang (Archives of Toxicology, 2017)

Chemical constituents from the roots of Ampelopsis delavayana and their antibacterial activities - Shuang-Xi Mei; Xu-Hong Li; Li-Guo Yang; Xiao-Hui Li; Jia-Ying Xie; Qi Yao; Mei Su; Tao Cui; Jing-Kun Wang; Zhao-Yun Zhu (Natural Product Research, 2017)

NMR-Based Metabolomics Reveal a Recovery from Metabolic Changes in the Striatum of 6-OHDA-Induced Rats Treated with Basic Fibroblast Growth Factor - Hong Zheng; Liangcai Zhao; Huanhuan Xia; Cuicui Xu; Dan Wang; Kun Liu; Li Lin; Xiaokun Li; Zhihan Yan; Hongchang Gao (Molecular Neurobiology, 2016)

Genome-wide scans reveal variants at EDAR predominantly affecting hair straightness in Han Chinese and Uyghur populations - Sijie Wu; Jingze Tan; Yajun Yang; Qianqian Peng; Manfei Zhang; Jinxi Li; Dongsheng Lu; Yu Liu; Haiyi Lou; Qidi Feng; Yan Lu; Yaqun Guan; et al. (Human Genetics, 2016)

The inulin-type oligosaccharides extract from morinda officinalis, a traditional Chinese herb, ameliorated behavioral deficits in an animal model of post-traumatic stress disorder - Zhi-Kun Qiu; Chun-Hui Liu; Zhuo-Wei Gao; Jia-Li He; Xu Liu; Qing-Lan Wei; Ji-Sheng Chen (Metabolic Brain Disease, 2016)

Benchmark dose for cadmium exposure and elevated N-acetyl-β-d-glucosaminidase: a meta-analysis - CuiXia Liu; YuBiao Li; ChunShui Zhu; ZhaoMin Dong; Kun Zhang; YanBin Zhao; YiLu Xu (Environmental Science and Pollution Research, 2016)

Identification of microRNAs, phasiRNAs and Their Targets in Pineapple - Yun Zheng; Ting Li; Zhenning Xu; Ching Man Wai; Kun Chen; Xiaotuo Zhang; Shengpeng Wang; Bo Ji; Ray Ming; Ramanjulu Sunkar (Tropical Plant Biology, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Organic two-photon nanoparticles modulate reactive oxygen species, intracellular calcium concentration, and mitochondrial membrane potential during apoptosis of human gastric carcinoma SGC-7901 cells - Geng Chen; Shou-Ying Li; Hamid Tayyab Malik; Yu-Guang Ma; Hong Xu; Lian-Kun Sun (Biotechnology Letters, 2016)

Glacier change in the western Nyainqentanglha Range, Tibetan Plateau using historical maps and Landsat imagery: 1970-2014 - Kun-peng Wu; Shi-yin Liu; Wan-qin Guo; Jun-feng Wei; Jun-li Xu; Wei-jia Bao; Xiao-jun Yao (Journal of Mountain Science, 2016)

Oceanobacillus endoradicis sp. nov., an endophytic bacterial species isolated from the root of Paris polyphylla Smith var. yunnanensis - Ling-Ling Yang; Shu-Kun Tang; Xiao Chu; Zhao Jiang; Li-Hua Xu; Xiao-Yang Zhi (Antonie van Leeuwenhoek, 2016)

Peanut regeneration by somatic embryogenesis (SE), involving bulbil-like body (BLB), a new type of SE structure - Kedong Xu; Bingyan Huang; Kun Liu; Feiyan Qi; Guangxuan Tan; Chengwei Li; Xinyou Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Melatonin improves antioxidant capacity and ion homeostasis and enhances salt tolerance in maize seedlings - Chaoqiang Jiang; Quanren Cui; Kun Feng; Dafeng Xu; Chengfeng Li; Qingsong Zheng (Acta Physiologiae Plantarum, 2016)

Adverse effect of DEHP exposure on the serum insulin level of Balb/c mice - Jing Wang; Jinquan Li; Kashif Rafiq Zahid; Kun Wang; Yan Qian; Ping Ma; Shumao Ding; Xu Yang; Xianliang Wang (Molecular & Cellular Toxicology, 2016)

Pro-neurogenic effect of β-asarone on RSC96 Schwann cells in vitro - Fuben Xu; Huayu Wu; Kun Zhang; Peizhen Lv; Li Zheng; Jinmin Zhao (In Vitro Cellular & Developmental Biology - Animal, 2016)

PGC-1α regulates the cell cycle through ATP and ROS in CH1 cells - Xu-feng Fu; Kun Yao; Xing Du; Yan Li; Xiu-yu Yang; Min Yu; Mei-zhang Li; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2016)

Intrathymic Tfh/B Cells Interaction Leads to Ectopic GCs Formation and Anti-AChR Antibody Production: Central Role in Triggering MG Occurrence - Xiaoyan Zhang; Shasha Liu; Ting Chang; Jiang Xu; Chunmei Zhang; Feng Tian; Yuanjie Sun; Chaojun Song; Wei Yi; Hong Lin; Zhuyi Li; Kun Yang (Molecular Neurobiology, 2016)

EDARV370A associated facial characteristics in Uyghur population revealing further pleiotropic effects - Qianqian Peng; Jinxi Li; Jingze Tan; Yajun Yang; Manfei Zhang; Sijie Wu; Yu Liu; Juan Zhang; Pengfei Qin; Yaqun Guan; Yi Jiao; Zhaoxia Zhang; et al. (Human Genetics, 2016)

RETRACTED ARTICLE: CXCR4 Signaling Induced Epithelial-Mesenchymal Transition by PI3K/AKT and ERK Pathways in Glioblastoma - Baoyu Lv; Xiangshan Yang; Shunzeng Lv; Lei Wang; Kaixi Fan; Ranran Shi; Fengling Wang; Huishu Song; Xiaochen Ma; Xuefen Tan; Kun Xu; Jingjing Xie; et al. (Molecular Neurobiology, 2015)

Modeling the interaction of an internal solitary wave with a sill - Qun Li; Zhenhua Xu; Baoshu Yin; Tao Bai; Kun Liu; Yang Wang (Acta Oceanologica Sinica, 2015)

Construction of a high-density linkage map and mapping quantitative trait loci for somatic embryogenesis using leaf petioles as explants in upland cotton (Gossypium hirsutum L.) - Zhenzhen Xu; Chaojun Zhang; Xiaoyang Ge; Ni Wang; Kehai Zhou; Xiaojie Yang; Zhixia Wu; Xueyan Zhang; Chuanliang Liu; Zuoren Yang; Changfeng Li; Kun Liu; et al. (Plant Cell Reports, 2015)

Isolation and characterization of AaAER, a novel double bond reductase from Artemisia annua - Yu-Kun Wei; Jian-Xu Li; Wen-Li Hu; Chang-Qing Yang; Ling-Jian Wang (Journal of Plant Biochemistry and Biotechnology, 2015)

Development of genic cleavage markers in association with seed glucosinolate content in canola - Ying Fu; Kun Lu; Lunwen Qian; Jiaqin Mei; Dayong Wei; Xuhui Peng; Xinfu Xu; Jiana Li; Martin Frauen; Felix Dreyer; Rod J. Snowdon; Wei Qian (Theoretical and Applied Genetics, 2015)

Effects of grassland degradation and re-vegetation on carbon and nitrogen storage in the soils of the Headwater Area Nature Reserve on the Qinghai-Tibetan Plateau, China - Xu-kun Su; Yu Wu; Shi-kui Dong; Lu Wen; Yuan-yuan Li; Xue-xia Wang (Journal of Mountain Science, 2015)

Oral cavity contains distinct niches with dynamic microbial communities - Xin Xu; Jinzhi He; Jing Xue; Yan Wang; Kun Li; Keke Zhang; Qiang Guo; Xianghong Liu; Yuan Zhou; Lei Cheng; Mingyun Li; Yuqing Li; et al. (Environmental Microbiology, 2015)
Summary Microbes colonize human oral surfaces within hours after delivery. During postnatal development, physiological changes, such as the eruption of primary teeth and replacement of the primary dentition with permanent dentition, greatly alter the microbial habitats, which, in return, may lead to community composition shifts at different phases in people's lives. By profiling saliva, supragingival and mucosal plaque samples from healthy volunteers at different ages and dentition stages, we observed that the oral cavity is a highly heterogeneous ecological system containing distinct niches with significantly different microbial communities. More importantly, the phylogenetic microbial structure varies with ageing. In addition, only a few taxa were present across the whole populations, indicating a core oral microbiome should be defined based on age and oral niches.

Insulin-like growth factors I and II in starry flounder (Platichthys stellatus): molecular cloning and differential expression during embryonic development - Yongjiang Xu; Kun Zang; Xuezhou Liu; Bao Shi; Cunyu Li; Xueying Shi (Fish Physiology and Biochemistry, 2015)

Assessment of association between the dopamine D2 receptor (DRD2) polymorphism and neurodevelopment of children exposed to lead - Lian Liu; Xijin Xu; Taofeek Akangbe Yekeen; Kun Lin; Weiqiu Li; Xia Huo (Environmental Science and Pollution Research, 2015)

Toll-like receptor 4-mediated nuclear factor-κB activation in spinal cord contributes to chronic morphine-induced analgesic tolerance and hyperalgesia in rats - Liying Bai; Caihong Zhai; Kun Han; Zhisong Li; Junliang Qian; Ying Jing; Wei Zhang; Ji-Tian Xu (Neuroscience Bulletin, 2014)

The Effect and Clinical Application of Homemade Tracheotomy Incision Nursing Pads - Yachun Yao; Li Xu; Kun Du; Jiajun Zhang (Cell Biochemistry and Biophysics, 2014)

Genome-wide investigation of genetic changes during modern breeding of Brassica napus - Nian Wang; Feng Li; Biyun Chen; Kun Xu; Guixin Yan; Jiangwei Qiao; Jun Li; Guizhen Gao; Ian Bancroft; Jingling Meng; Graham J. King; Xiaoming Wu (Theoretical and Applied Genetics, 2014)

The protective effect of rosmarinic acid on hyperthermia-induced C2C12 muscle cells damage - Kun-Lin Chen; Hui-Xia Li; Xing-Lian Xu; Guang-Hong Zhou (Molecular Biology Reports, 2014)

Evaluation of yield and agronomic traits and their genetic variation in 488 global collections of Brassica napus L. - Biyun Chen; Kun Xu; Jun Li; Feng Li; Jiangwei Qiao; Hao Li; Guizhen Gao; Guixin Yan; Xiaoming Wu (Genetic Resources and Crop Evolution, 2014)

Evaluation of snow depth and snow cover fraction simulated by two versions of the flexible global ocean-atmosphere-land system model - Kun Xia; Bin Wang; Lijuan Li; Si Shen; Wenyu Huang; Shiming Xu; Li Dong; Li Liu (Advances in Atmospheric Sciences, 2014)

Targeted disruption of the sheep MSTN gene by engineered zinc-finger nucleases - Cunfang Zhang; Ling Wang; Gang Ren; Zhanwei Li; Chonghua Ren; Tingting Zhang; Kun Xu; Zhiying Zhang (Molecular Biology Reports, 2014)

Variability of atlantic meridional overturning circulation in FGOALS-g2 - Wenyu Huang; Bin Wang; Lijuan Li; Li Dong; Pengfei Lin; Yongqiang Yu; Tianjun Zhou; Li Liu; Shiming Xu; Kun Xia; Ye Pu; Lu Wang; et al. (Advances in Atmospheric Sciences, 2014)

Differential Expression of the CBF Gene Family During Postharvest Cold Storage and Subsequent Shelf-Life of Peach Fruit - Li Liang; Bo Zhang; Xue-Ren Yin; Chang-Jie Xu; Chong-De Sun; Kun-Song Chen (Plant Molecular Biology Reporter, 2013)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Stachybotrys from soil in China, identified by morphology and molecular phylogeny - Chun-Yu Jie; Kun Geng; Yu-Lan Jiang; Jun-Jie Xu; Kevin D. Hyde; Eric H. C. McKenzie; Tian-Yu Zhang; Ali H. Bahkali; De-Wei Li; Yong Wang (Mycological Progress, 2013)

Two new vinblastine-type N -oxide alkaloids from Catharanthus roseus - Wei-Ku Zhang; Jie-Kun Xu; Hai-Yan Tian; Lei Wang; Xiao-Qi Zhang; Xu-Zhi Xiao; Ping Li; Wen-Cai Ye (Natural Product Research, 2013)

POPs and their ecological risk in sewage sludge of waste water treatment plants in Beijing, China - Cao Liu; Kun Li; Liqin Yu; Yiping Xu; Bingbin Huang; Jingdong Wu; Zijian Wang (Stochastic Environmental Research and Risk Assessment, 2013)

Fine root production, turnover, and decomposition in a fast-growth Eucalyptus urophylla plantation in southern China - Weiqiang Xu; Juxiu Liu; Xingzhao Liu; Kun Li; Deqiang Zhang; Junhua Yan (Journal of Soils and Sediments, 2013)

Themoanaerobacterium calidifontis sp. nov., a novel anaerobic, thermophilic, ethanol-producing bacterium from hot springs in China - Shu-mei Shang; Long Qian; Xu Zhang; Kun-zhi Li; Irbis Chagan (Archives of Microbiology, 2013)

Strategy for pH control and pH feedback-controlled substrate feeding for high-level production of l-tryptophan by Escherichia coli - Li-Kun Cheng; Jian Wang; Qing-Yang Xu; Chun-Guang Zhao; Zhi-Qiang Shen; Xi-Xian Xie; Ning Chen (World Journal of Microbiology and Biotechnology, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

Simulation of sea ice in FGOALS-g2: Climatology and late 20th century changes - Shiming Xu; Mirong Song; Jiping Liu; Bin Wang; Lijuan Li; Wenyu Huang; Li Liu; Kun Xia; Wei Xue; Ye Pu; Li Dong; Si Shen; et al. (Advances in Atmospheric Sciences, 2013)

Preliminary evaluations of FGOALS-g2 for decadal predictions - Bin Wang; Mimi Liu; Yongqiang Yu; Lijuan Li; Pengfei Lin; Li Dong; Li Liu; Jiping Liu; Wenyu Huang; Shiming Xu; Si Shen; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

The flexible global ocean-atmosphere-land system model, Grid-point Version 2: FGOALS-g2 - Lijuan Li; Pengfei Lin; Yongqiang Yu; Bin Wang; Tianjun Zhou; Li Liu; Jiping Liu; Qing Bao; Shiming Xu; Wenyu Huang; Kun Xia; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

Walleye dermal sarcoma virus: expression of a full-length clone or the rv-cyclin (orf a) gene is cytopathic to the host and human tumor cells - Kun Xu; Ting Ting Zhang; Ling Wang; Cun Fang Zhang; Long Zhang; Li Xia Ma; Ying Xin; Chong Hua Ren; Zhi Qiang Zhang; Qiang Yan; Daniel Martineau; Zhi Ying Zhang (Molecular Biology Reports, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Erratum to: Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Loss-of-function mutations in filaggrin gene associate with psoriasis vulgaris in Chinese population - Zhengmao Hu; Zhimin Xiong; Xiaojuan Xu; Fangfang Li; Lina Lu; Wei Li; Juan Su; Yalan Liu; Deyuan Liu; Zhiguo Xie; Yu Peng; Yehong Kuang; et al. (Human Genetics, 2012)

Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Transdifferentiation of human adipose-derived stem cells into urothelial cells: potential for urinary tract tissue engineering - Jian-Guo Shi; Wei-Jun Fu; Xiao-Xiong Wang; Yong-De Xu; Gang Li; Bao-Fa Hong; Kun Hu; Fu-Zhai Cui; Yan Wang; Xu Zhang (Cell and Tissue Research, 2012)

Channelized fluids in subducted continental crust: constraints from δD–δ 18 O of quartz and fluid inclusions in quartz veins from the Chinese Continental Scientific Drilling Project - Xiaoming Sun; Li Xu; Weidong Sun; Wei Zhai; Yeheng Liang; Qian Tang; Jinlong Liang; Zeming Zhang; Kun Shen; Fangyue Wang; Mingxing Ling; Robert E. Zartman (International Geology Review, 2011)

Fungistatic Intensity of Agricultural Soil Against Fungal Agents and Phylogenetic Analysis on the Actinobacteria Involved - Li Zhi Fang; Xu Chuan Kun; Zou Chang Song; Xi Jia Qin; He Yue Qiu; Duan Chang Qun; Mo Ming He (Current Microbiology, 2011)

Effects of selected genetic polymorphisms in xeroderma pigmentosum complementary group D on gastric cancer - Ziping Chen; Chuanzhen Zhang; Changqing Xu; Kun Li; Ruiping Hou; Danping Li; Xiaoli Cheng (Molecular Biology Reports, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

Nocardiopsis terrae sp. nov., a halophilic actinomycete isolated from saline soil - Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Zhu-Xiang Liu; Li-Hua Xu; Li-Xin Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Coordinated regulation of anthocyanin biosynthesis in Chinese bayberry (Myrica rubra) fruit by a R2R3 MYB transcription factor - Shan-Shan Niu; Chang-Jie Xu; Wang-Shu Zhang; Bo Zhang; Xian Li; Kui Lin-Wang; Ian B. Ferguson; Andrew C. Allan; Kun-Song Chen (Planta, 2010)

Mycotoxin Ochratoxin A-induced cell death and changes in oxidative metabolism of Arabidopsis thaliana - Xiao-Li Peng; Wen-Tao Xu; Yan Wang; Kun-Lun Huang; Zhi-hong Liang; Wei-wei Zhao; Yun-Bo Luo (Plant Cell Reports, 2010)

Atrazine degradation by a simple consortium of Klebsiella sp. A1 and Comamonas sp. A2 in nitrogen enriched medium - Chunyu Yang; Yang Li; Kun Zhang; Xia Wang; Cuiqing Ma; Hongzhi Tang; Ping Xu (Biodegradation, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Relationships between endothelial nitric oxide synthase gene polymorphisms and osteoporosis in postmenopausal women - Shun-zhi Liu; Hong Yan; Wei-kun Hou; Peng Xu; Juan Tian; Li-fang Tian; Bo-feng Zhu; Jie Ma; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2009)

The characteristics and parameterization of aerodynamic roughness length over heterogeneous surfaces - Li Lu; Shaomin Liu; Ziwei Xu; Kun Yang; Xuhui Cai; Li Jia; Jiemin Wang (Advances in Atmospheric Sciences, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

New BZLF1 sequence variations in EBV-associated undifferentiated nasopharyngeal carcinoma in southern China - Kun-Mei Ji; Chun-Lin Li; Guang Meng; Ai-Dong Han; Xu-Li Wu (Archives of Virology, 2008)

Characterization of cDNAs associated with lignification and their expression profiles in loquat fruit with different lignin accumulation - Lan Lan Shan; Xian Li; Ping Wang; Chong Cai; Bo Zhang; Chong De Sun; Wang Shu Zhang; Chang Jie Xu; Ian Ferguson; Kun Song Chen (Planta, 2008)

Streptomyces serianimatus sp. nov., isolated from a rhizophere soil - Yong-Xia Wang; Xiao-Yang Zhi; Hua-Hong Chen; Yu-Qin Zhang; Shu Kun Tang; Cheng-Lin Jiang; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2007)

Functional analysis of the α-neurotoxin, BmαTX14, derived from the Chinese scorpion, Buthus martensii Karsch - Kun Wang; Shi-Jin Yin; Meng Lu; Hong Yi; Chao Dai; Xiu-Jing Xu; Zhi-Jian Cao; Ying-Liang Wu; Wen-Xin Li (Biotechnology Letters, 2006)

Isolation and Characterization of a Carbendazim-Degrading Rhodococcus sp. djl-6 - Xu Jing-Liang; Gu Xiang-Yang; Shen Biao; Wang Zhi-Chun; Wang Kun; Li Shun-Peng (Current Microbiology, 2006)

Streptomyces daliensis sp. nov. from soil - Ping Xu; Wen-Jun Li; Shu-Kun Tang; Hui-Ying Gao; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2006)

A novel technique of three-dimensional reconstruction segmentation and analysis for sliced images of biological tissues - Jing Li; Hai-yan Zhao; Xing-yun Ruan; Yong-qing Xu; Wei-zheng Meng; Kun-peng Li; Jing-qiang Zhang (Journal of Zhejiang University-SCIENCE B, 2005)

Development of a rapid, reliable and simple multiplex PCR assay for early detection of transgenic plant materials - Chang-Jie Xu; Li Yang; Kun-Song Chen (Acta Physiologiae Plantarum, 2005)

Green fluorescent protein as a vital elimination marker to easily screen marker-free transgenic progeny derived from plants co-transformed with a double T-DNA binary vector system - Songbiao Chen; Xugang Li; Xiang Liu; Hongling Xu; Kun Meng; Guifang Xiao; Xiaoli Wei; Feng Wang; Zhen Zhu (Plant Cell Reports, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)